Anti-aging nanocellulose-based reinforced modified material and preparation method thereof

By combining load-modified mica nanosheets and phosphorylated nanocellulose in nanocellulose-based reinforced modified materials, the problem of uneven dispersion of nanocellulose in polymer materials is solved, and the anti-aging of composite materials is significantly improved , mechanical and flame retardant properties.

CN119490698APending Publication Date: 2025-02-21天津永续新材料有限公司 +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411692192.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

When nanocellulose is used as a filler in polymer materials, due to the strong polarity of the surface hydroxyl group, it is easy to agglomerate with the matrix material, resulting in uneven dispersion, poor compatibility, and poor thermal stability, which affects the mechanical properties of the composite material.

Method used

Anti-aging nanocellulose-based reinforced modified materials were prepared by combining the load-modified mica nanosheets and phosphorylated nanocellulose. The material obtains mica nanosheets through ultrasonic peeling and spray drying techniques, and improves its hydrophobicity by modification of silane coupling agent. Phosphorylation treatment improves the mechanical strength and flame retardant properties of nanocellulose.

Benefits of technology

The anti-aging, mechanical properties and flame retardant properties of the composite material are significantly improved. Through the synergy between load-modified mica nanosheets and phosphorylated nanocellulose, better dispersion uniformity and mechanical properties are achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119490698A_ABST
    Figure CN119490698A_ABST
Patent Text Reader

Abstract

The invention provides an anti-aging nanocellulose-based reinforced modified material and a preparation method thereof, and the preparation method comprises the following steps: sequentially carrying out phosphorylation treatment and nanocrystallization treatment on a cellulose raw material to obtain phosphorylated nanocellulose; the preparation method comprises the following steps: uniformly mixing phosphorylated nanocellulose, load modified mica nanosheets, a nonionic surfactant and deionized water to obtain a composite suspension, carrying out ultrasonic dispersion on the composite suspension to obtain a composite dispersion liquid, and carrying out spray drying on the composite dispersion liquid to obtain the nanocellulose-based reinforced modified material. According to the invention, the loaded modified mica nanosheet and the phosphorylated nanocellulose are compounded to prepare the anti-aging nanocellulose-based reinforced modified material, and the reinforced modified material can be used as a performance enhancer of high polymer materials such as coatings, rubber, plastics, foods, medical materials and the like to improve the product structure and improve the physical and chemical properties of the product; the anti-aging property, the mechanical property, the flame-retardant property and the like are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of enhanced modified materials, and relates to an anti-aging nano-cellulose-based enhanced modified material and a preparation method thereof. Background Art

[0002] Cellulose is the most abundant, renewable, biocompatible and biodegradable natural polymer on earth. With the emergence and development of nanotechnology, cellulose has attracted more and more attention in the new form of "nanocellulose". In addition to the advantages of a wide range of raw material sources, non-toxicity, renewable and biodegradable, nanocellulose also has the characteristics of large specific surface area, high aspect ratio, good water retention, low density and high strength. It has excellent performance in high-performance reinforced composite materials, medical materials, optical materials and other fields.

[0003] When nanocellulose is used as a filler in polymer materials to prepare composite materials, it is easy to agglomerate when mixed with matrix materials because of its rich hydroxyl groups on its surface and strong polarity, resulting in uneven dispersion, poor compatibility, poor thermal stability and other problems in the matrix, thereby affecting the mechanical properties of the composite materials. Therefore, how to improve the compatibility of nanocellulose with the matrix material and give the composite material certain anti-aging properties is a technical problem to be solved by the present invention. Summary of the invention

[0004] In view of the shortcomings of the prior art, the purpose of the present invention is to provide an anti-aging nano-cellulose-based reinforced modified material and a preparation method thereof. The present invention compounded loaded modified mica nanosheets and phosphorylated nano-cellulose to prepare an anti-aging nano-cellulose-based reinforced modified material. The reinforced modified material can be used as a performance enhancer for polymers such as coatings, rubbers, plastics, foods, and medical materials to improve the product structure and enhance the physical and chemical properties of the product, such as anti-aging properties, mechanical properties, and flame retardant properties.

[0005] To achieve this object, the present invention adopts the following technical solutions:

[0006] In a first aspect, the present invention provides a method for preparing an anti-aging nanocellulose-based enhanced modified material, the preparation method comprising:

[0007] (I) subjecting sericite to high temperature calcination to obtain activated sericite; subjecting the activated sericite to acidification with a nitric acid solution to obtain acidified sericite; subjecting the acidified sericite to lithiation with lithium nitrate to obtain lithiated sericite; subjecting the lithiated sericite to intercalation modification with hexadecyltrimethylammonium bromide to obtain intercalated sericite; subjecting the intercalated sericite to ultrasonic exfoliation to obtain mica nanosheets;

[0008] (II) mixing deionized water, dichloromethane and ethanol to obtain a composite solvent, and dropping an acetic acid solution into the composite solvent to adjust the pH value thereof; dropping a silane coupling agent into the composite solvent, mixing and stirring to cause hydrolysis, and obtaining a silane coupling agent solution; dispersing the mica nanosheets obtained in step (I) in the silane coupling agent solution, mixing and stirring under a water bath heating condition to cause a reaction, and filtering, washing and drying after the reaction to obtain modified mica nanosheets;

[0009] (III) dispersing the modified mica nanosheets obtained in step (II) in deionized water to obtain a mica dispersion, adding a manganese source solution to the mica dispersion under stirring conditions, mixing evenly, and then performing a hydrothermal reaction to obtain an intermediate reaction solution; adding a tetrabutyl titanate solution to the intermediate reaction solution under stirring conditions, mixing evenly, and then performing a secondary hydrothermal reaction, and then filtering, washing and drying to obtain loaded modified mica nanosheets;

[0010] (IV) sequentially subjecting the cellulose raw material to phosphorylation and nano-processing to obtain phosphorylated nanocellulose; uniformly mixing the phosphorylated nanocellulose, the loaded modified mica nanosheets obtained in step (III), a nonionic surfactant and deionized water to obtain a composite suspension, ultrasonically dispersing the composite suspension to obtain a composite dispersion, and spray-drying the composite dispersion to obtain the nanocellulose-based enhanced modified material.

[0011] The present invention compounds the loaded modified mica nanosheets and the phosphorylated nanocellulose to prepare an anti-aging nanocellulose-based enhanced modified material, which can be used as a performance enhancer for polymers such as coatings, rubbers, plastics, foods, and pharmaceutical materials to improve the product structure and improve the physical and chemical properties of the product, such as anti-aging performance, mechanical properties, and flame retardant properties. When used, the enhanced modified material provided by the present invention can be added to the base material in a certain proportion, mixed evenly, and then produced according to conventional processes. For example, in the field of coatings, the enhanced modified material provided by the present invention can be added to the coating emulsion in a certain proportion, mixed evenly, and then coated. After drying and forming a film, a paint film coating with excellent anti-aging performance, mechanical properties, and flame retardant properties can be obtained; in the field of plastics, the enhanced modified material provided by the present invention can be melt-blended and extruded with a polymer material in a certain proportion to obtain a plastic masterbatch with excellent anti-aging performance, mechanical properties, and flame retardant properties.

[0012] In the present invention, there is a synergistic effect between the loaded modified mica nanosheets and the phosphorylated nanocellulose, which is specifically embodied in:

[0013] On the one hand, phosphorylated nanocellulose is a fiber-like structure with a large specific surface area and a high aspect ratio. It has high mechanical strength. When added to a matrix material (such as coatings, plastics, rubber, etc.), it can form a three-dimensional network structure skeleton in the polymer matrix. When the loaded modified mica nanosheets are uniformly loaded on the three-dimensional network structure skeleton, the phosphorylated nanocellulose can become a "physical bridge" between the loaded modified mica nanosheets. When subjected to external forces, the load stress can be smoothly transferred to avoid stress concentration leading to composite material fracture. In addition, since the loaded modified mica nanosheets are modified by silane coupling agents, their surfaces contain some silanol groups, which can be combined with the free hydroxyl groups existing in large quantities on the surface of phosphorylated nanocellulose to produce strong hydrogen bonding. There is also a hydrogen bonding force between phosphorylated nanocellulose and the matrix material. Therefore, phosphorylated nanocellulose can also serve as a "chemical bridge" between the matrix material and the loaded modified mica nanosheets. Through the dual effects of "physical bridge" and "chemical bridge", the dispersion uniformity of the loaded modified mica nanosheets in the polymer matrix is ​​greatly improved, thereby significantly improving the mechanical properties of the composite material.

[0014] On the other hand, the loaded modified mica nanosheets tend to be arranged parallel to the surface of the composite material. Since the loaded modified mica nanosheets are sheet-like structures, they are elastic and can slide, and can form a highly inert, solid and flexible protective film on the surface of the composite material that resists chemical corrosion and solar radiation. This protective film can effectively prevent the penetration of atmosphere and moisture, thereby playing a barrier and protective role for the interior of the composite material. Combined with the mechanical enhancement properties of phosphorylated nanocellulose itself, on the one hand, a three-dimensional network structure skeleton can be formed inside the composite material, and on the other hand, the dispersion uniformity of the loaded modified mica nanosheets in the matrix material can be significantly improved. The synergistic effect between phosphorylated nanocellulose and loaded modified mica nanosheets can significantly improve the anti-aging and flame retardant properties of the composite material.

[0015] Mica nanosheets are a two-dimensional sheet filler. After adding an appropriate amount of mica nanosheets to the matrix material, the barrier property of the composite material surface can be significantly improved to provide good anti-aging performance. The present invention uses sericite as a raw material, and obtains mica nanosheets through high-temperature activation, acidification, lithiation, intercalation modification and ultrasonic stripping. However, due to the hydrophilicity of mica nanosheets, the dispersibility in the matrix material is poor and they are easy to agglomerate in the matrix material, which hinders the advantages of mica nanosheets in the composite material. Therefore, the present invention hydrophobically modifies the mica nanosheets to improve their uniformity of dispersion in the matrix material.

[0016] Sericite is a silicate mineral with a layered structure. During the high-temperature activation process, the OH -Desorption and conversion into interlayer water. During the calcination process, the temperature difference between the inside and outside of the sericite flakes is large, resulting in a large temperature gradient between the middle and edge areas of the flakes. The interlayer water discharge rate in the edge area is faster, and the water is enriched around the sericite, sealing the internal space between the layers of the sericite. Water loss and sealing occurs in the edge area of ​​the sericite flakes, making it difficult to discharge the water in the middle area of ​​the layer, resulting in a higher vapor pressure in the middle area of ​​the layer, forcing the sericite flakes to expand, which is beneficial to the subsequent organic intercalation treatment of hexadecyltrimethylammonium bromide.

[0017] The physical and chemical structure of sericite is composed of two layers of silicon-oxygen tetrahedron [(Si,Al)-O 4 ] and the middle layer of aluminum oxide octahedron [AlO 2 (OH) 4 ] The interlayer cations are mainly potassium ions and magnesium ions. Since potassium ions and magnesium ions have larger ion radius, higher charge density and larger ion hydration number, there are more water molecules around potassium ions and magnesium ions and they are more firmly bound, which makes potassium ions and magnesium ions lose their ion exchange capacity, which is not conducive to organic intercalation modification. At the same time, potassium ions are just embedded in two hexagonal meshes facing each other on adjacent crystal planes, forming 12 times coordination, and the interlayer charge is close to neutrality. The potassium ions are very tightly bound to the crystal planes, and the interlayer spacing is relatively fixed, which makes the exchangeable ion concentration of sericite low and the interlayer charge very stable. Even if the sheets expand after high-temperature activation, due to the weak ion exchange capacity, it is difficult for hexadecyltrimethylammonium bromide to enter the interlayers of sericite through ion exchange for intercalation modification. To this end, the present invention performs acidification and lithiation treatment on the sericite after high-temperature activation, thereby increasing the interlamellar spacing of the sericite through high-temperature activation and increasing the exchangeable ion concentration between the sericite lamellae through acidification and lithiation, thereby greatly promoting the organic intercalation modification of hexadecyltrimethylammonium bromide.

[0018] Since Al-O tetrahedron is not as stable as Si-O tetrahedron, acid treatment of sericite can destroy Al-O tetrahedron, preferentially dissolve Al in tetrahedron and deplete it, thus destroying interlayer ionization balance and enhancing interlayer activity. 3 O +It can replace most of the interlayer magnesium ions and dissolve a small amount of cations in the aluminum oxide octahedron, so that some impurities between the sericite sheets are dissolved by acid, the interlayer channels are unblocked, and the diffusion and adsorption capacity of molecules between the layers is improved. In addition, after acid treatment, a large number of fine grooves appear on the surface of the sericite sheets, which increases the surface roughness, ion adsorption area and surface electrical properties of the sericite, and improves the ion exchange capacity between the sericite sheets. After acid treatment, some interlayer ions such as aluminum ions, magnesium ions, calcium ions and potassium ions are dissolved, and the interlayer charge is destroyed. Subsequently, lithium treatment is performed to further improve the interlayer ion exchange capacity of sericite. Since the ion radius of lithium ions is relatively small, the charge density is low, the binding energy between the sheets of sericite is weak, the hydration energy is low, and the hydration ion radius is large, the cations are easier to exchange ions with the outside world, thereby increasing the exchangeable ion concentration between the sericite sheets, which is beneficial to organic intercalation modification.

[0019] Through the early high-temperature activation, acidification and lithiation treatment, the layers of sericite have exchangeable water molecules and cations. At this time, the concentration of exchangeable cations is relatively high, and the hexadecyltrimethylammonium bromide molecules can enter the layers of sericite through cation exchange to obtain intercalated sericite. When the ammonium ions in hexadecyltrimethylammonium bromide enter the sericite lamellae through ion exchange, the sericite lamellae are stretched open by the cleavage plane, and the alkyl chains then enter the lamellae. After entering the lamellae, hexadecyltrimethylammonium bromide adopts the most stable spatial form for arrangement. When the concentration of hexadecyltrimethylammonium bromide is low, the alkyl chains are arranged parallel to the lamellae surface. As the concentration of hexadecyltrimethylammonium bromide increases, the alkyl chains continue to enter the interlayers of sericite, the angle with the lamellae surface becomes larger, and the single layer is transformed into a double layer until the concentration of hexadecyltrimethylammonium bromide increases to form a double-layer structure and arrange at a large angle. Due to the spatial form and distribution of the alkyl chains between the sericite lamellae, the spacing between the sericite lamellae is forced to expand. Under the action of ultrasonic-assisted exfoliation, the overlapping lamellae of sericite are finally completely exfoliated to form mica nanosheets.

[0020] The present invention uses a silane coupling agent to hydrophobically modify mica nanosheets. The silane coupling agent is hydrolyzed under the action of deionized water to generate silanols. The generated silanols undergo a condensation reaction to form silane oligomers. The silane oligomers further react with hydroxyl groups on the surface of the mica nanosheets to generate silicon-oxygen bonds after dehydration condensation, thereby being grafted on the surface of the mica nanosheets, thereby achieving hydrophobic modification of the mica nanosheets. The present invention adds dichloromethane as a promoter of the coupling grafting reaction in the composite solvent. In the composite solvent, dichloromethane and deionized water form an oil-water interface, which is conducive to promoting the coupling grafting reaction between the silane coupling agent and the mica nanosheets, and effectively improving the reaction efficiency of the silane coupling agent and the mica nanosheets.

[0021] Modification with silane coupling agent can also improve the mechanical reinforcement effect of the modified mica nanosheets. This is because the silane coupling agent plays a cross-linking role between the modified mica nanosheets, which increases the cross-linking density of the composite material added with the enhanced modified material provided by the present invention, reduces cracks and holes on the surface and inside of the composite material, and makes the final composite material denser, giving the composite material higher mechanical properties.

[0022] Composite materials will age when exposed to sunlight for a long time, resulting in cracks or even breakage on their surfaces. The present invention uses a hydrothermal method to load titanium dioxide, an inorganic UV shielding material, on modified mica nanosheets. Titanium dioxide has a narrow bandgap and a high refractive index, and a wide UV absorption range. In particular, nanoscale titanium dioxide has a larger specific surface area and can produce a stronger absorption and scattering effect on ultraviolet rays. It is an excellent UV shielding material. However, titanium dioxide also has defects such as poor shielding performance in the long-wave part of the ultraviolet region, easy aggregation of particles, and difficulty in regulating the particle morphology. The present invention uses a hydrothermal synthesis method to load titanium dioxide particles on the surface of modified mica nanosheets, which can solve the above problems well. This is because:

[0023] On the one hand, there are many dangling bonds on the surface of modified mica nanosheets, so its structure has a tendency to adsorb heteroelectric substances. At the same time, the unique layer structure of modified mica nanosheets can cause the incident light to produce multiple reflections and refractions between layers. These characteristics make the modified mica nanosheets a good carrier of titanium dioxide, improve the uniformity of the dispersion of titanium dioxide in the matrix material, and effectively solve the problem of easy agglomeration of titanium dioxide in the polymer matrix; on the other hand, with the help of the layer structure of the modified mica sheet, an optical trap is formed, which can significantly enhance the ultraviolet shielding effect of titanium dioxide and make up for the defect of poor shielding performance of titanium dioxide for the long-wave part of the ultraviolet region. Through the synergistic effect of modified mica nanosheets and titanium dioxide, the ultraviolet shielding effect of nanocellulose-based reinforced modified materials is improved, making the composite material have excellent anti-aging properties.

[0024] On the other hand, common titanium dioxide loading processes include liquid phase precipitation, sol-gel and physical blending, wherein the liquid phase precipitation method is difficult to control the particle size of titanium dioxide, the sol-gel method may destroy the lamellar structure of the modified mica nanosheet during the roasting process, and the physical blending method will cause the loaded titanium dioxide to be not firm and easy to fall off. Therefore, the present invention adopts a hydrothermal synthesis method to synthesize titanium dioxide in situ on the surface of modified mica nanosheets, and compared with the liquid phase precipitation method, the particle size of titanium dioxide can be effectively controlled by the process conditions of the hydrothermal synthesis method; compared with the high temperature calcination treatment of the sol-gel method, the treatment temperature of the hydrothermal synthesis method is relatively low, and the structure, morphology and properties of the modified mica nanosheet will not be adversely affected; compared with the physical blending method, the hydrothermal synthesis method can synthesize titanium dioxide in situ on the surface of the modified mica nanosheet, and the combination between titanium dioxide and the modified mica nanosheet is more firm and not easy to fall off.

[0025] Aging test analysis shows that the anti-aging properties of the composite material can be greatly improved by loading titanium dioxide. This is because the loaded modified mica nanosheets added to the polymer matrix have high UV absorption properties, which can effectively absorb and scatter the ultraviolet rays entering the composite material, weakening the photo-oxidation reaction of the composite material caused by ultraviolet irradiation, thereby greatly reducing the damage caused by ultraviolet rays to the polymer molecular chain structure in the composite material, and avoiding a significant decrease in the mechanical properties of the composite material during the aging process.

[0026] The present invention prepares phosphorylated nanocellulose through phosphorylation and nano-processing, and adding it to a polymer matrix can significantly improve the mechanical properties and flame retardant properties of the composite material. This is because, on the one hand, the phosphorylated nanocellulose has a crystalline region and a non-crystalline region along the length of the cellulose molecular chain, the crystalline region has a large density and has natural hydrophobic properties, and the three-dimensional hydrogen bond network structure formed between and within the phosphorylated nanocellulose molecules gives the composite material higher mechanical properties. On the other hand, after phosphorylation, the decarboxylation and dehydration reactions of the phosphorylated nanocellulose can be promoted, and the carbonization process of the phosphorylated nanocellulose can be accelerated, so that the peak heat release rate time is advanced, and the residual rate of the phosphorylated nanocellulose is higher. After combustion, more coke layers are attached to the surface of the composite material, which can form a physical barrier, play a role in heat insulation protection, and suppress the combustion behavior; in addition, the non-combustible gases (such as H 2 O、CO 2 ) can also effectively dilute the combustible gas, thereby reducing the temperature in the combustion zone and further reducing the possibility of combustion, significantly improving the flame retardant properties of the composite material.

[0027] In addition, when the composite reinforcement material provided by the present invention is used in a coating, the rheological properties of the coating can be significantly improved. This is because the phosphorylated nanocellulose in the composite reinforcement material has a large number of exposed hydroxyl functional groups on its surface, which can form hydrogen bonds with the emulsion in the coating; at the same time, strong hydrogen bonding is also generated between the phosphorylated nanocelluloses, so that the phosphorylated nanocelluloses are cross-linked with each other to form a stable three-dimensional network structure, which can give the coating excellent rheological properties. The three-dimensional network structure formed by the hydrogen bonding is temporarily destroyed under the action of shear force, resulting in a decrease in the viscosity of the coating. When the shear force is removed, the three-dimensional network structure is re-formed, and the viscosity of the coating is increased again, so that the coating exhibits rheological properties and has a shear-thinning effect, which can be used to improve the sedimentation of the coating during storage and the pseudoplastic characteristics during construction.

[0028] As a preferred technical solution of the present invention, in step (I), the heating temperature of the high temperature calcination is 750-850°C, for example, it can be 750°C, 760°C, 770°C, 780°C, 790°C, 800°C, 810°C, 820°C, 830°C, 840°C or 850°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0029] In an optional embodiment, the holding time for high temperature calcination is 1 to 2 hours, for example, it can be 1.0h, 1.1h, 1.2h, 1.3h, 1.4h, 1.5h, 1.6h, 1.7h, 1.8h, 1.9h or 2.0h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0030] In an optional example, the acidification process includes: dispersing the activated sericite in a nitric acid solution, mixing, stirring and heating, and then filtering, washing and drying to obtain the acidified sericite.

[0031] In an optional example, the concentration of the nitric acid solution is 8~12 mol / L, for example, it can be 8 mol / L, 8.5 mol / L, 9 mol / L, 9.5 mol / L, 10 mol / L, 10.5 mol / L, 11 mol / L, 11.5 mol / L or 12 mol / L, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0032] The present invention particularly limits the concentration of the nitric acid solution to 8-12 mol / L, and the amount of aluminum ions dissolved increases with the increase of the concentration of the nitric acid solution, because the higher the concentration of hydrogen ions, the more favorable it is for adsorption on the sericite crystal surface, thereby destroying the Al-O bond and Si-O bond in the lamella lattice, and dissolving the aluminum ions in the tetrahedron and octahedron. Since the hydrogen ions first replace the cations such as potassium ions and sodium ions between the layers after entering the lamella, and then dissolve the aluminum ions and silicon ions with four-coordinate and six-coordinate coordination, therefore, in a high-concentration hydrogen ion environment, after the replacement and dissolution of part of the aluminum ions, there are still high-concentration hydrogen ions to promote the further dissolution of the aluminum ions. When the concentration of the nitric acid solution exceeds the upper limit of the range defined in the present invention, the dissolution efficiency of aluminum ions gradually decreases. This is related to the aluminum ion content in the sericite flakes and the aluminum ion concentration in the solution. As the nitric acid solution continuously dissolves aluminum ions, the concentration of aluminum ions in the surface layer of the sericite continues to decrease, while the concentration of aluminum ions in the solution near the contact surface continues to increase, prompting the replacement and aluminum ion dissolution to reach a chemical equilibrium, ultimately reducing the dissolution rate of aluminum ions.

[0033] In an optional example, the ratio of the activated sericite to the nitric acid solution is (2~4) g:100 mL, for example, it can be 2.0 g:100 mL, 2.2 g:100 mL, 2.4 g:100 mL, 2.6 g:100 mL, 2.8 g:100 mL, 3.0 g:100 mL, 3.2 g:100 mL, 3.4 g:100 mL, 3.6 g:100 mL, 3.8 g:100 mL or 4.0 g:100 mL, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0034] In an optional example, the mixing and stirring time of the activated sericite and the nitric acid solution is 4 to 5 hours, for example, it can be 4.0 hours, 4.1 hours, 4.2 hours, 4.3 hours, 4.4 hours, 4.5 hours, 4.6 hours, 4.7 hours, 4.8 hours, 4.9 hours or 5.0 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0035] In an optional example, the temperature for mixing the activated sericite and the nitric acid solution is 80-90°C, for example, 80°C, 81°C, 82°C, 83°C, 84°C, 85°C, 86°C, 87°C, 88°C, 89°C or 90°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0036] In an optional example, the lithiation process includes:

[0037] The acidified sericite and lithium nitrate are uniformly mixed to obtain a mixed powder; the mixed powder is sent into a muffle furnace for calcination to obtain a calcined powder, and the calcined powder is filtered, washed and dried to obtain the lithiated sericite.

[0038] In an optional example, the mass ratio of the acidified sericite to the lithium nitrate is 1:(8~10), for example, it can be 1:8.0, 1:8.2, 1:8.4, 1:8.6, 1:8.8, 1:9.0, 1:9.2, 1:9.4, 1:9.6, 1:9.8 or 1:10.0, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0039] In an optional embodiment, the calcination temperature of the mixed powder is 300-400°C, for example, it can be 300°C, 310°C, 320°C, 330°C, 340°C, 350°C, 360°C, 370°C, 380°C, 390°C or 400°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0040] In an optional example, the calcination time of the mixed powder is 5 to 6 hours, for example, it can be 5.0h, 5.1h, 5.2h, 5.3h, 5.4h, 5.5h, 5.6h, 5.7h, 5.8h, 5.9h or 6.0h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0041] The present invention particularly limits the calcination time of the mixed powder to 5 to 6 hours. When the calcination time is less than 5 hours, the lithium ions lack sufficient time to replace the interlayer cations, and the lithium modification effect is not ideal. As the reaction time increases, there is sufficient time for the ion exchange reaction, and the finally obtained lithiated sericite has a high cation exchange capacity, which provides a sufficient number of exchangeable cations for the later organic intercalation modification, so that the organic intercalation modification can be carried out smoothly. When the calcination time exceeds 6 hours, the ion exchange reaction reaches equilibrium, and the number of exchangeable cations between the sericite sheets reaches saturation. Continuing to increase the calcination time will not only fail to increase the cation exchange concentration between the sericite sheets, but also affect the sheet structure of the sericite, so that the barrier property of the mica nanosheets is reduced, and the anti-aging performance of the composite material is affected.

[0042] As a preferred technical solution of the present invention, in step (I), the intercalation modification process includes:

[0043] The lithiated sericite is dispersed in deionized water to obtain a sericite solution, hexadecyltrimethylammonium bromide is added to the sericite solution, the mixture is stirred and heated, and then the intercalated sericite is obtained after filtering, washing and drying.

[0044] In an optional example, the mixing ratio of the lithiated sericite and deionized water is (0.8~1.3) g:100 mL, for example, it can be 0.8g:100mL, 0.85g:100mL, 0.9g:100mL, 0.95g:100mL, 1g:100mL, 1.05g:100mL, 1.1g:100mL, 1.15g:100mL, 1.2g:100mL, 1.25g:100mL or 1.3g:100mL, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0045] In an optional example, the mass ratio of the lithiated sericite to hexadecyltrimethylammonium bromide in the sericite solution is 1:(2.5~3.5), for example, it can be 1:2.5, 1:2.6, 1:2.7, 1:2.8, 1:2.9, 1:3.0, 1:3.1, 1:3.2, 1:3.3, 1:3.4 or 1:3.5, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0046] The present invention specifically limits the mass ratio of lithiated sericite to hexadecyltrimethylammonium bromide in the sericite solution to 1:(2.5-3.5). With the increase of the amount of hexadecyltrimethylammonium bromide, the interlayer spacing of the mica nanosheets finally obtained shows a trend of first increasing and then decreasing. When the mass ratio of lithiated sericite to hexadecyltrimethylammonium bromide is within the numerical range defined by the present invention, a larger interlayer spacing can be obtained and a higher intercalation efficiency can be achieved. When the amount of hexadecyltrimethylammonium bromide is lower than the lower limit of the range defined by the present invention, the interlayer cations of the sericite cannot be completely exchanged by the hexadecyltrimethylammonium bromide chain, resulting in a smaller interlayer spacing of the intercalated sericite, and effective ultrasonic stripping cannot be achieved. When the amount of hexadecyltrimethylammonium bromide used exceeds the upper limit of the range defined in the present invention, too many organic chains tend to accumulate in the interlayer edge region of sericite, blocking the exchange channel between the organic chains and the interlayer cations, resulting in only a small number of hexadecyltrimethylammonium bromide molecular chains being able to successfully enter the interlayers of sericite, replacing lithium ions to achieve organic intercalation modification, while most of the hexadecyltrimethylammonium bromide molecular chains are unable to successfully enter the interlayers of sericite, but are simply adsorbed on the surface of sericite, resulting in low intercalation efficiency.

[0047] In an optional example, the mixing and stirring time of the sericite solution and hexadecyltrimethylammonium bromide is 2 to 3 hours, for example, it can be 2.0 hours, 2.1 hours, 2.2 hours, 2.3 hours, 2.4 hours, 2.5 hours, 2.6 hours, 2.7 hours, 2.8 hours, 2.9 hours or 3.0 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0048] In an optional example, the temperature for mixing and stirring the sericite solution and hexadecyltrimethylammonium bromide is 70-80°C, for example, 70°C, 71°C, 72°C, 73°C, 74°C, 75°C, 76°C, 77°C, 78°C, 79°C or 80°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0049] As a preferred technical solution of the present invention, in step (I), the ultrasonic peeling process includes:

[0050] The intercalated sericite is dispersed in ethanol, ultrasonically exfoliated to obtain a sericite dispersion, the sericite dispersion is centrifuged once, the supernatant after the first centrifugation is centrifuged twice, and the precipitate after the second centrifugation is washed and dried to obtain the mica nanosheets.

[0051] In an optional example, the mass ratio of the intercalated sericite to ethanol is 1:(4~5), for example, it can be 1:4.0, 1:4.1, 1:4.2, 1:4.3, 1:4.4, 1:4.5, 1:4.6, 1:4.7, 1:4.8, 1:4.9 or 1:5.0, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0052] In an optional example, the ultrasonic power of the ultrasonic peeling is 400~500W, for example, it can be 400W, 410W, 420W, 430W, 440W, 450W, 460W, 470W, 480W, 490W or 500W, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0053] In an optional example, the ultrasonic time of the ultrasonic stripping is 2 to 3 hours, for example, it can be 2.0h, 2.1h, 2.2h, 2.3h, 2.4h, 2.5h, 2.6h, 2.7h, 2.8h, 2.9h or 3.0h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0054] In an optional example, the rotation speed of the centrifugation is 2000~3000r / min, for example, it can be 2000r / min, 2100r / min, 2200r / min, 2300r / min, 2400r / min, 2500r / min, 2600r / min, 2700r / min, 2800r / min, 2900r / min or 3000r / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0055] In an optional example, the centrifugation time is 10 to 20 min, for example, it can be 10 min, 11 min, 12 min, 13 min, 14 min, 15 min, 16 min, 17 min, 18 min, 19 min or 20 min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0056] In an optional example, the rotation speed of the secondary centrifugation is 2000-3000 r / min, for example, it can be 2000 r / min, 2100 r / min, 2200 r / min, 2300 r / min, 2400 r / min, 2500 r / min, 2600 r / min, 2700 r / min, 2800 r / min, 2900 r / min or 3000 r / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0057] In an optional example, the secondary centrifugation time is 10 to 20 min, for example, it can be 10 min, 11 min, 12 min, 13 min, 14 min, 15 min, 16 min, 17 min, 18 min, 19 min or 20 min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0058] As a preferred technical solution of the present invention, in step (II), in the composite solvent, the volume ratio of deionized water, dichloromethane and ethanol is 1:(1.3-1.5):(0.5-0.7), for example, it can be 1:1.3:0.5, 1:1.32:0.52, 1:1.34:0.54, 1:1.36:0.56, 1:1.38:0.58, 1:1.4:0.6, 1:1.42:0.62, 1:1.44:0.64, 1:1.46:0.66, 1:1.48:0.68 or 1:1.5:0.7, but it is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0059] The present invention particularly limits the volume ratio of deionized water, dichloromethane and ethanol in the composite solvent to 1:(1.3-1.5):(0.5-0.7), and the deionized water and ethanol respectively promote and inhibit the hydrolysis reaction of the silane coupling agent, so that the hydrolysis reaction of the silane coupling agent reaches a dynamic equilibrium, which can effectively improve the stability of the silane coupling agent solution, thereby improving the hydrophobic modification effect of the silane coupling agent on the mica nanosheets.

[0060] As the amount of ethanol increases, the conductivity of the silane coupling agent solution gradually increases, which indicates that an appropriate amount of ethanol can also promote the hydrolysis of the silane coupling agent. However, when the amount of ethanol exceeds the upper limit of the range defined in the present invention, further increasing the amount of ethanol will cause the conductivity of the silane coupling agent solution to show a downward trend, because a large amount of hydroxyl groups in ethanol inhibit the hydrolysis of the silane coupling agent and hinder the formation of silanols.

[0061] In an optional embodiment, acetic acid solution is added dropwise to the composite solvent to adjust its pH value to 4.5-5.5, for example, it can be 4.5, 4.6, 4.7, 4.8, 4.9, 5.0, 5.1, 5.2, 5.3, 5.4 or 5.5, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0062] In an optional example, the volume ratio of the silane coupling agent to the composite solvent is 1:(15-20), for example, 1:15, 1:15.5, 1:16, 1:16.5, 1:17, 1:17.5, 1:18, 1:18.5, 1:19, 1:19.5 or 1:20, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0063] In an optional embodiment, the mixing and stirring time of the silane coupling agent and the composite solvent is 0.5 to 1.5 h, for example, it can be 0.5 h, 0.6 h, 0.7 h, 0.8 h, 0.9 h, 1.0 h, 1.1 h, 1.2 h, 1.3 h, 1.4 h or 1.5 h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0064] In an optional example, the ratio of the mica nanosheets to the silane coupling agent in the silane coupling agent solution is 1g:(0.05~0.06)mL, for example, it can be 1g:0.05mL, 1g:0.051mL, 1g:0.052mL, 1g:0.053mL, 1g:0.054mL, 1g:0.055mL, 1g:0.056mL, 1g:0.057mL, 1g:0.058mL, 1g:0.059mL or 1g:0.06mL, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0065] The present invention particularly limits the ratio of mica nanosheets to the silane coupling agent in the silane coupling agent solution to 1 g: (0.05-0.06) mL. When the amount of the silane coupling agent exceeds the upper limit of the range defined by the present invention, the hydrophobic modification effect on the mica nanosheets will deteriorate. This is because when the amount of the silane coupling agent is too high, the silane coupling agent itself will undergo a polymerization reaction, resulting in a reduction in the amount of the silane coupling agent coupled and grafted with the mica nanosheets, and the hydrophobicity of the obtained modified mica nanosheets is reduced.

[0066] In an optional example, the mixing and stirring time of the mica nanosheets and the silane coupling agent solution is 30 to 60 minutes, for example, 30 minutes, 35 minutes, 40 minutes, 45 minutes, 50 minutes, 55 minutes or 60 minutes, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0067] The present invention specifically limits the mixing and stirring time of the mica nanosheets and the silane coupling agent solution to 30 to 60 minutes. Within this range, the contact angle of the modified mica nanosheets obtained is the largest and the hydrophobicity is the highest. When the mixing and stirring time reaches 60 minutes, the coupling grafting reaction between the mica nanosheets and the hydrolysis product silanol of the silane coupling agent has been fully carried out. As the reaction time continues to extend, the silanols produced by the hydrolysis of the silane coupling agent undergo a dehydration condensation reaction, thereby inhibiting the coupling grafting reaction between the silanol and the mica nanosheets.

[0068] In an optional example, the temperature for mixing and stirring the mica nanosheets and the silane coupling agent solution is 70-80°C, for example, 70°C, 71°C, 72°C, 73°C, 74°C, 75°C, 76°C, 77°C, 78°C, 79°C or 80°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0069] As a preferred technical solution of the present invention, in step (III), the mass fraction of the modified mica nanosheets in the mica flake dispersion is 8-10wt%, for example, it can be 8.0wt%, 8.2wt%, 8.4wt%, 8.6wt%, 8.8wt%, 9.0wt%, 9.2wt%, 9.4wt%, 9.6wt%, 9.8wt% or 10.0wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0070] In an optional example, the manganese source solution consists of potassium permanganate, manganese sulfate and deionized water.

[0071] In an optional example, the concentration of potassium permanganate in the manganese source solution is 7-8 g / mL, for example, 7.0 g / mL, 7.1 g / mL, 7.2 g / mL, 7.3 g / mL, 7.4 g / mL, 7.5 g / mL, 7.6 g / mL, 7.7 g / mL, 7.8 g / mL, 7.9 g / mL or 8.0 g / mL, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0072] In an optional example, in the manganese source solution, the mass ratio of potassium permanganate to manganese sulfate is (6-8):1, for example, it can be 6.0:1, 6.2:1, 6.4:1, 6.6:1, 6.8:1, 7.0:1, 7.2:1, 7.4:1, 7.6:1, 7.8:1 or 8.0:1, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0073] In an optional example, the mass ratio of the modified mica nanosheets to the potassium permanganate in the manganese source solution is 1:(0.1~0.2), for example, it can be 1:0.1, 1:0.11, 1:0.12, 1:0.13, 1:0.14, 1:0.15, 1:0.16, 1:0.17, 1:0.18, 1:0.19 or 1:0.2, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0074] The present invention particularly limits the mass ratio of the modified mica nanosheets to the potassium permanganate in the manganese source solution to 1:(0.1-0.2), the amount of potassium permanganate used will directly affect the generated amount of manganese dioxide obtained after the hydrothermal synthesis reaction, and the generated amount of manganese dioxide will further affect the crystal form of hydrothermally synthesized titanium dioxide. There are two common crystal forms of titanium dioxide, namely rutile type and anatase type. Compared with anatase type titanium dioxide, rutile type titanium dioxide has a narrower bandgap width, has a good reflection effect on light in the visible light and ultraviolet region of the spectrum, and has a stronger ultraviolet light absorption performance.

[0075] When the amount of potassium permanganate is lower than the lower limit of the range defined in the present invention, the manganese dioxide obtained by the hydrothermal synthesis reaction is less, and the titanium dioxide obtained is mainly anatase-type. As the amount of potassium permanganate increases, the amount of manganese dioxide generated also gradually increases, resulting in a gradual decrease in the amount of anatase-type titanium dioxide generated and a gradual increase in the amount of rutile-type titanium dioxide generated. This is because the presence of manganese dioxide can induce the anatase-type titanium dioxide to transform into the rutile type; in addition, manganese dioxide and titanium dioxide can form a composite semiconductor, and manganese dioxide as a deep energy level impurity can promote the recombination of photogenerated electrons and holes in titanium dioxide, thereby enhancing the ultraviolet absorption efficiency of the manganese dioxide / titanium dioxide composite. When the amount of potassium permanganate exceeds the upper limit of the range defined in the present invention, the amount of manganese dioxide generated is too high, which will lead to a decrease in the amount of rutile titanium dioxide generated and anatase titanium dioxide generated. This is because the amount of rutile titanium dioxide generated has tended to be saturated and cannot provide additional active reaction sites. Excess manganese dioxide will aggregate on the surface of the modified mica nanosheets, weakening the crystal induction effect of manganese dioxide, thereby affecting the ultraviolet absorption ability of the loaded modified mica nanosheets.

[0076] In an optional embodiment, the reaction temperature of the hydrothermal reaction is 130-150°C, for example, it can be 130°C, 132°C, 134°C, 136°C, 138°C, 140°C, 142°C, 144°C, 146°C, 148°C or 150°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0077] In an optional example, the reaction time of the hydrothermal reaction is 4 to 5 h, for example, 4.0 h, 4.1 h, 4.2 h, 4.3 h, 4.4 h, 4.5 h, 4.6 h, 4.7 h, 4.8 h, 4.9 h or 5.0 h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0078] In an optional example, before adding the tetrabutyl titanate solution to the intermediate reaction solution, a hydrochloric acid solution is first added to the intermediate reaction solution to adjust its pH value to 3-5, for example, 3.0, 3.2, 3.4, 3.6, 3.8, 4.0, 4.2, 4.4, 4.6, 4.8 or 5.0, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0079] In order to obtain rutile titanium dioxide nanocrystals, the present invention particularly selects hydrochloric acid solution as an acid inhibitor. Different acid inhibitors produce titanium dioxide with different crystal forms. Acetic acid solution is generally easy to produce anatase titanium dioxide, while hydrochloric acid solution and nitric acid solution are easy to produce rutile titanium dioxide. The present invention controls the reaction conditions of the hydrothermal synthesis reaction so that anatase titanium dioxide is converted into rutile titanium dioxide as completely as possible.

[0080] After the hydrolysis of tetrabutyl titanate, amorphous titanium dioxide is generated. After adding hydrochloric acid solution, the amorphous titanium dioxide will be dissolved into extremely fine titanium dioxide nanocrystals. The pH value mainly controls the alkoxide metal Ti(OR) 4 The hydrolysis and condensation of the modified mica nanosheets affect the bonding barrier in the growth process of titanium dioxide grains. Therefore, the pH value has a great influence on the morphology, structure and crystal form of titanium dioxide loaded on the surface of modified mica nanosheets.

[0081] The present invention specifically limits the addition of hydrochloric acid solution to the intermediate reaction solution to adjust its pH value to 3-5. When the pH value is lower than 3, the obtained titanium dioxide particles are monodispersed nano-spherical structures, with a small specific surface area and a small number of reactive sites; at the same time, the titanium dioxide loaded on the surface of the modified mica nanosheets is mainly anatase-type titanium dioxide, and the ultraviolet absorption intensity is relatively low. With the increase of the pH value, the particle size of the titanium dioxide spherical particles gradually increases. When the pH value is increased to 5, the titanium dioxide particles loaded on the surface of the modified mica nanosheets are combined by a number of small particles to form large particles. At this time, the specific surface area of ​​the titanium dioxide particles is large, and the number of reactive sites increases. At the same time, the generation amount of rutile titanium dioxide increases with the increase of the pH value. The titanium dioxide loaded on the surface of the modified mica nanosheets is mainly rutile titanium dioxide, and the ultraviolet absorption intensity of the obtained loaded modified mica nanosheets is relatively high. When the pH value continues to increase to more than 5, the titanium dioxide particles loaded on the surface of the modified mica nanosheets are nanoflower-like structures composed of several nanorods, the specific surface area is reduced, and the reaction active sites are reduced. At the same time, too high a pH value will cause the proportion of rutile titanium dioxide in the loaded modified mica nanosheets to decrease and the proportion of anatase titanium dioxide to increase, ultimately causing the ultraviolet absorption intensity of the loaded modified mica nanosheets to decrease.

[0082] In an optional example, the concentration of the hydrochloric acid solution is 5~10mol / L, for example, it can be 5.0mol / L, 5.5mol / L, 6.0mol / L, 6.5mol / L, 7.0mol / L, 7.5mol / L, 8.0mol / L, 8.5mol / L, 9.0mol / L, 9.5mol / L or 10.0mol / L, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0083] In an optional example, the tetrabutyl titanate solution consists of tetrabutyl titanate, ethanol and deionized water.

[0084] In an optional embodiment, in the tetrabutyl titanate solution, the volume ratio of tetrabutyl titanate, ethanol and deionized water is (10-20):(80-100):(40-50), for example, it can be 10:80:40, 11:82:41, 12:84:42, 13:86:43, 14:88:44, 15:90:45, 16:92:46, 17:94:47, 18:96:48, 19:98:49 or 20:100:50, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0085] In an optional example, the mass ratio of the modified mica nanosheets to the tetrabutyl titanate in the tetrabutyl titanate solution is 1:(0.5~0.6), for example, it can be 1:0.5, 1:0.51, 1:0.52, 1:0.53, 1:0.54, 1:0.55, 1:0.56, 1:0.57, 1:0.58, 1:0.59 or 1:0.6, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0086] A single modified mica nanosheet has a certain ultraviolet absorption intensity in the ultraviolet region (200~500nm). This is because the lamellar structure of the modified mica nanosheet can cause the incident light to be reflected and refracted multiple times between layers, thereby giving the modified mica nanosheet a certain ultraviolet shielding ability. When the surface of the modified mica nanosheet is loaded with manganese dioxide / titanium dioxide to form a loaded modified mica nanosheet, its ultraviolet absorption intensity can be greatly enhanced.

[0087] When the amount of tetrabutyl titanate is too small, the amount of titanium dioxide generated by the hydrothermal synthesis reaction is small, and the ultraviolet absorption capacity of the finally obtained loaded modified mica nanosheet is weak. As the amount of titanium dioxide generated increases, the ultraviolet absorption intensity of the loaded modified mica nanosheet also increases. This is because, on the one hand, the increase in the amount of titanium dioxide generated increases the specific surface area of ​​the loaded modified mica nanosheet, and the number of photoreactive sites increases; on the other hand, the proportion of rutile titanium dioxide on the surface of the loaded modified mica nanosheet increases, so that the ultraviolet absorption intensity of the loaded modified mica nanosheet increases accordingly. When the amount of tetrabutyl titanate reaches the upper limit of the range defined by the present invention, the ultraviolet absorption intensity of the loaded modified mica nanosheet decreases instead. This is because, when the amount of titanium dioxide generated by the hydrothermal synthesis reaction is too high, the surface of the loaded modified mica nanosheet will form a messy, loose, uneven coating state, which reduces the number of photoreactive sites.

[0088] In an optional embodiment, the reaction temperature of the secondary hydrothermal reaction is 150-160°C, for example, it can be 150°C, 151°C, 152°C, 153°C, 154°C, 155°C, 156°C, 157°C, 158°C, 159°C or 160°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0089] In an optional example, the reaction time of the secondary hydrothermal reaction is 5 to 6 hours, for example, it can be 5.0 hours, 5.1 hours, 5.2 hours, 5.3 hours, 5.4 hours, 5.5 hours, 5.6 hours, 5.7 hours, 5.8 hours, 5.9 hours or 6.0 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0090] As a preferred technical solution of the present invention, in step (IV), the phosphorylation treatment comprises:

[0091] The cellulose raw material is subjected to steam explosion to obtain raw fiber, the raw fiber, phosphate, urea and deionized water are mixed to obtain a suspension, the suspension is heated and crushed at the same time to obtain a mixed material; the mixed material is sent to a screw extruder for extrusion dehydration to obtain a wet material; the wet material is heated and dried and high-temperature cured in sequence to obtain phosphorylated cellulose.

[0092] In the process of preparing phosphorylated nanocellulose, the present invention first performs steam explosion on the cellulose raw material, and steam explosion is to treat the cellulose raw material with hot steam under a certain pressure, and then perform explosive decompression on the cellulose raw material. This pretreatment combines the chemical action of the self-hydrolysis of acetyl groups in hemicellulose with mechanical action. In the hot steam treatment process, the cellulose raw material is under high temperature and high pressure conditions, and water vapor will penetrate into the interior of the fiber molecules, and part of the water vapor will form hydrogen bonds with the hydroxyl groups in the fiber molecules, destroying the hydrogen bonding between the original hydroxyl groups in the interior of the cellulose molecules. After the pressure is suddenly released, the water molecules will burst instantly under the negative pressure, and this phenomenon is also called the cavitation effect, which causes the cellulose to produce mechanical fractures, and the hydrogen bonds formed by water vapor and the interior of the cellulose will disappear, which is conducive to the cavitation effect to play a role, destroying the force between the molecules inside the fiber, and the fiber is separated due to the mechanical action. In addition, high temperature promotes the generation of carboxyl groups by acetyl groups, and hemicellulose begins to self-hydrolyze. At the same time, water can also play the role of acid, and as part of the hemicellulose is dissolved or degraded, lignin is redistributed and partially removed. The separation of cellulose and the removal of hemicellulose fully expose the surface of cellulose, which promotes the interaction between phosphate and urea and cellulose. The steam explosion treatment can significantly improve the thermal stability and flame retardant properties of the fiber.

[0093] After the steam explosion treatment, the raw fiber obtained by the present invention is heated, soaked and broken up in a mixed solution of phosphate and urea, so that the raw fiber is fully swollen, and the phosphate and urea are caused to penetrate into the structure of the raw fiber and be fully adsorbed. On the one hand, the adsorption modification of phosphate is conducive to obtaining phosphorylated nanocellulose with high charge and flame retardant performance, and the phosphorylated nanocellulose with high charge is more conducive to its uniform dispersion in the matrix material. On the other hand, urea as a nitrogen flame retardant is a synergist of phosphate flame retardant, because the nitrogen-containing gas can promote the expansion of the residue and can be used as an inert gas to dilute the fuel, so that the charred layer is rich in carbon, and the generated gas contains fewer carbon atoms, which ultimately leads to lower combustion heat.

[0094] The present invention adopts mechanical screw extrusion dehydration to remove part of the flowing liquid in the mixture, reduce the water content of the mixture, and further reduce the energy consumption of the subsequent heating drying and high-temperature curing process. During the extrusion dehydration process, the mixture moves forward under the action of gravity and the friction between the mixture and the screw, which produces an extrusion effect on the mixture. The water in the mixture is discharged through the drainage hole of the screw extruder. As the mixture is continuously transmitted along the screw, the water in the mixture is continuously extruded and discharged; at the same time, a shearing effect is generated between the mixture and the screw. The mixture is squeezed and sheared by the screw, causing the cellulose in the mixture to be twisted, cut, separated, and swollen. The fiber cell wall in the mixture is further destroyed to form a loose structure area, which is more conducive to the penetration and infiltration of phosphate and urea.

[0095] In an alternative embodiment, the cellulosic raw material includes bleached hardwood pulp or bleached softwood pulp.

[0096] In an optional example, the steam pressure of the steam explosion is 1-2 MPa, for example, 1.0 MPa, 1.1 MPa, 1.2 MPa, 1.3 MPa, 1.4 MPa, 1.5 MPa, 1.6 MPa, 1.7 MPa, 1.8 MPa, 1.9 MPa or 2.0 MPa, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0097] In an optional embodiment, the steam temperature of the steam explosion is 180-200°C, for example, it can be 180°C, 182°C, 184°C, 186°C, 188°C, 190°C, 192°C, 194°C, 196°C, 198°C or 200°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0098] In an optional example, the processing time of the steam explosion is 5 to 10 min, for example, it can be 5.0 min, 5.5 min, 6.0 min, 6.5 min, 7.0 min, 7.5 min, 8.0 min, 8.5 min, 9.0 min, 9.5 min or 10.0 min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0099] In an optional example, the mass fraction of the raw fiber in the suspension is 5~10wt%, for example, it can be 5.0wt%, 5.5wt%, 6.0wt%, 6.5wt%, 7.0wt%, 7.5wt%, 8.0wt%, 8.5wt%, 9.0wt%, 9.5wt% or 10.0wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0100] In an optional example, the concentration of phosphate in the suspension is 0.2~0.3kg / L, for example, it can be 0.2kg / L, 0.21kg / L, 0.22kg / L, 0.23kg / L, 0.24kg / L, 0.25kg / L, 0.26kg / L, 0.27kg / L, 0.28kg / L, 0.29kg / L or 0.3kg / L, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0101] In an optional example, the phosphate includes any one of diammonium hydrogen phosphate, ammonium dihydrogen phosphate, disodium hydrogen phosphate, sodium dihydrogen phosphate, dilithium hydrogen phosphate or lithium dihydrogen phosphate, or a combination of at least two thereof.

[0102] In an optional example, the concentration of urea in the suspension is 0.4-0.5 kg / L, for example, it can be 0.4 kg / L, 0.41 kg / L, 0.42 kg / L, 0.43 kg / L, 0.44 kg / L, 0.45 kg / L, 0.46 kg / L, 0.47 kg / L, 0.48 kg / L, 0.49 kg / L or 0.5 kg / L, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0103] In an optional embodiment, the heating temperature of the suspension is 60-80°C, for example, it can be 60°C, 62°C, 64°C, 66°C, 68°C, 70°C, 72°C, 74°C, 76°C, 78°C or 80°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0104] In an optional embodiment, the heating time of the suspension is 2 to 3 hours, for example, it can be 2.0 hours, 2.1 hours, 2.2 hours, 2.3 hours, 2.4 hours, 2.5 hours, 2.6 hours, 2.7 hours, 2.8 hours, 2.9 hours or 3.0 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0105] In an optional embodiment, the screw speed of the screw extruder is 10~20rpm, for example, it can be 10rpm, 11rpm, 12rpm, 13rpm, 14rpm, 15rpm, 16rpm, 17rpm, 18rpm, 19rpm or 20rpm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0106] In an optional example, the moisture content of the wet material is 60-70wt%, for example, it can be 60wt%, 61wt%, 62wt%, 63wt%, 64wt%, 65wt%, 66wt%, 67wt%, 68wt%, 69wt% or 70wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0107] In an optional embodiment, the heating and drying temperature is 80-90°C, for example, it can be 80°C, 81°C, 82°C, 83°C, 84°C, 85°C, 86°C, 87°C, 88°C, 89°C or 90°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0108] In an optional embodiment, the heating and drying time is 40 to 50 minutes, for example, it can be 40 minutes, 41 minutes, 42 minutes, 43 minutes, 44 minutes, 45 minutes, 46 minutes, 47 minutes, 48 ​​minutes, 49 minutes or 50 minutes, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0109] In an optional embodiment, the high temperature curing temperature is 150-160°C, for example, it can be 150°C, 151°C, 152°C, 153°C, 154°C, 155°C, 156°C, 157°C, 158°C, 159°C or 160°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0110] In an optional example, the high temperature curing time is 20 to 30 minutes, for example, it can be 20 minutes, 21 minutes, 22 minutes, 23 minutes, 24 minutes, 25 minutes, 26 minutes, 27 minutes, 28 minutes, 29 minutes or 30 minutes, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0111] As a preferred technical solution of the present invention, in step (IV), the operation steps of the nano-treatment include:

[0112] The phosphorylated cellulose is mixed with deionized water to obtain a cellulose mixed solution, and the cellulose mixed solution is subjected to mechanical grinding and high-pressure homogenization in sequence to obtain the phosphorylated nanocellulose.

[0113] In an optional example, the mass fraction of the phosphorylated cellulose in the cellulose mixture is 0.5-1.5wt%, for example, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1.0wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt% or 1.5wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0114] In an optional embodiment, the mechanical grinding is performed in a colloid mill.

[0115] In an optional embodiment, the rotation speed of the colloid mill is 2500~3000r / min, for example, it can be 2500r / min, 2550r / min, 2600r / min, 2650r / min, 2700r / min, 2750r / min, 2800r / min, 2850r / min, 2900r / min, 2950r / min or 3000r / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0116] In an optional embodiment, the mechanical grinding time is 2 to 3 hours, for example, it can be 2.0h, 2.1h, 2.2h, 2.3h, 2.4h, 2.5h, 2.6h, 2.7h, 2.8h, 2.9h or 3.0h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0117] In an optional example, the pressure of the high-pressure homogenization is 70~100MPa, for example, it can be 70MPa, 75MPa, 80MPa, 85MPa, 90MPa, 95MPa or 100MPa, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0118] In an optional example, the high-pressure homogenization time is 60 to 90 minutes, for example, it can be 60 minutes, 65 minutes, 70 minutes, 75 minutes, 80 minutes, 85 minutes or 90 minutes, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0119] As a preferred technical solution of the present invention, in step (IV), the mass fraction of the phosphorylated nanocellulose in the composite suspension is 1-2wt%, for example, it can be 1.0wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt%, 1.5wt%, 1.6wt%, 1.7wt%, 1.8wt%, 1.9wt% or 2.0wt%, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0120] In an optional example, the mass ratio of the phosphorylated nanocellulose to the loaded modified mica nanosheets is 1:(3~5), for example, it can be 1:3.0, 1:3.2, 1:3.4, 1:3.6, 1:3.8, 1:4.0, 1:4.2, 1:4.4, 1:4.6, 1:4.8 or 1:5.0, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0121] The present invention particularly limits the mass ratio of phosphorylated nanocellulose to loaded modified mica nanosheets to 1: (3-5), the addition of phosphorylated nanocellulose can exert its own mechanical strengthening effect, and can significantly improve the dispersibility of loaded modified mica nanosheets in the matrix material, avoid the loaded modified mica nanosheets from agglomerating in the polymer matrix, thereby causing stress concentration phenomenon, affecting the mechanical properties of the composite material. However, the amount of phosphorylated nanocellulose should not be too high, when the amount of phosphorylated nanocellulose exceeds the upper limit of the range defined by the present invention, it will cause the viscosity of the matrix material to be too high, which is not conducive to subsequent processing such as painting construction or melt extrusion. At the same time, the amount of loaded modified mica nanosheets should not be too high, when the amount of loaded modified mica nanosheets exceeds the upper limit of the range defined by the present invention, agglomeration phenomenon will still occur, thereby causing stress concentration phenomenon, affecting the mechanical properties of the composite material.

[0122] In an optional example, the mass fraction of the nonionic surfactant in the composite suspension is 0.5~1.5wt%, for example, it can be 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1.0wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt% or 1.5wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0123] In an optional example, the nonionic surfactant includes any one of ethoxylated fatty acid esters, alkanolamides, or fatty alcohol polyoxyethylene ethers, or a combination of at least two thereof.

[0124] In an optional embodiment, the ultrasonic power of the ultrasonic dispersion of the composite suspension is 400-500 W, for example, 400 W, 410 W, 420 W, 430 W, 440 W, 450 W, 460 W, 470 W, 480 W, 490 W or 500 W, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0125] In an optional example, the ultrasonic dispersion time of the composite suspension is 2 to 3 h, for example, 2.0 h, 2.1 h, 2.2 h, 2.3 h, 2.4 h, 2.5 h, 2.6 h, 2.7 h, 2.8 h, 2.9 h or 3.0 h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0126] In an optional example, the spray drying process of the composite dispersion is carried out in a spray drying tower.

[0127] In an optional embodiment, the inlet air temperature of the spray drying tower is 150-250°C, for example, it can be 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C or 250°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0128] In an optional embodiment, the outlet air temperature of the spray drying tower is 90-100°C, for example, it can be 90°C, 91°C, 92°C, 93°C, 94°C, 95°C, 96°C, 97°C, 98°C, 99°C or 100°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0129] In an optional embodiment, the feed rate of the spray drying tower is 50~100mL / h, for example, it can be 50mL / h, 55mL / h, 60mL / h, 65mL / h, 70mL / h, 75mL / h, 80mL / h, 85mL / h, 90mL / h, 95mL / h or 100mL / h, but is not limited to the listed values. In some optional embodiments, other unlisted values ​​within the numerical range are also applicable.

[0130] In a second aspect, the present invention provides an anti-aging nano-cellulose-based reinforced modified material prepared by the preparation method described in the first aspect.

[0131] Compared with the prior art, the present invention has the following beneficial effects:

[0132] The present invention compounds the loaded modified mica nanosheets and the phosphorylated nanocellulose to prepare an anti-aging nanocellulose-based enhanced modified material, which can be used as a performance enhancer for polymers such as coatings, rubbers, plastics, foods, and pharmaceutical materials to improve the product structure and improve the physical and chemical properties of the product, such as anti-aging performance, mechanical properties, and flame retardant properties. When used, the enhanced modified material provided by the present invention can be added to the base material in a certain proportion, mixed evenly, and then produced according to conventional processes. For example, in the field of coatings, the enhanced modified material provided by the present invention can be added to the coating emulsion in a certain proportion, mixed evenly, and then coated. After drying and forming a film, a paint film coating with excellent anti-aging performance, mechanical properties, and flame retardant properties can be obtained; in the field of plastics, the enhanced modified material provided by the present invention can be melt-blended and extruded with a polymer material in a certain proportion to obtain a plastic masterbatch with excellent anti-aging performance, mechanical properties, and flame retardant properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0133] Figure 1 A process flow chart for preparing the nanocellulose-based enhanced modified material provided in Examples 1-5 of the present invention;

[0134] Figure 2 This is a scanning electron microscope image of the sericite mica used in Example 1 of the present invention;

[0135] Figure 3 This is a scanning electron microscope image of the activated sericite prepared in Example 1 of the present invention;

[0136] Figure 4 This is a scanning electron microscope image of the acidified sericite prepared in Example 1 of the present invention;

[0137] Figure 5 The infrared spectra of sericite and mica nanosheets prepared in Example 1 of the present invention are shown;

[0138] Figure 6 This is an AFM image of the bleached hardwood pulp used in Example 1 of the present invention;

[0139] Figure 7 This is an AFM image of the raw material fiber prepared in Example 1 of the present invention;

[0140] Figure 8 This is a transmission electron microscopy image of the phosphorylated nanocellulose prepared in Example 1 of the present invention;

[0141] Fig. 9 This is a surface electron microscope image of a paint film formed by a water-based paint prepared with the nanocellulose-based enhanced modified material provided in Example 1 of the present invention before an aging test;

[0142] Fig.10 This is a surface electron microscope image of a paint film formed by a water-based paint prepared with the nanocellulose-based enhanced modified material provided in Example 1 of the present invention after an aging test;

[0143] Fig.11 This is a surface electron microscope image of a paint film formed by a water-based paint provided in a comparative example of the present invention before an aging test;

[0144] Fig.12 This is a surface electron microscope image of a paint film formed by a water-based paint provided as a comparative example of the present invention after aging test. DETAILED DESCRIPTION

[0145] The technical solution of the present invention is described in detail below in conjunction with specific embodiments and their accompanying drawings. The embodiments recorded herein are specific embodiments of the present invention, which are used to illustrate the concept of the present invention; these descriptions are explanatory and exemplary and should not be construed as limitations on the embodiments of the present invention and the scope of protection of the present invention. In addition to the embodiments recorded herein, those skilled in the art can also adopt other obvious technical solutions based on the contents disclosed in the claims of this application and its specification, including technical solutions that adopt any obvious replacements and modifications to the embodiments recorded herein.

[0146] Example 1

[0147] This embodiment provides a method for preparing an anti-aging nanocellulose-based enhanced modified material, such as Figure 1 As shown, the preparation method specifically comprises the following steps:

[0148] (1) calcining sericite at high temperature, wherein the heating temperature of the high temperature calcination is 750°C and the holding time is 2 hours, and activated sericite is obtained after calcination; the activated sericite is dispersed in a nitric acid solution with a concentration of 8 mol / L, and the ratio of the activated sericite to the nitric acid solution is 2 g:100 mL, and the mixture is mixed and stirred at 80°C for 5 hours, and then filtered, washed and dried to obtain acidified sericite; the acidified sericite and lithium nitrate are uniformly mixed in a mass ratio of 1:8 to obtain a mixed powder, and the mixed powder is fed into a muffle furnace, and calcined at 300°C for 6 hours to obtain a calcined powder, and the calcined powder is filtered, washed and dried to obtain lithiated sericite;

[0149] Dispersing lithiated sericite in deionized water, the mixing ratio of lithiated sericite to deionized water is 0.8 g:100 mL, and mixing evenly to obtain a sericite solution, adding hexadecyltrimethylammonium bromide to the sericite solution, the mass ratio of lithiated sericite to hexadecyltrimethylammonium bromide in the sericite solution is 1:2.5, mixing and stirring at 70° C. for 3 h, and then filtering, washing and drying to obtain intercalated sericite;

[0150] The intercalated sericite was dispersed in ethanol, the mass ratio of the intercalated sericite to ethanol was 1:4, ultrasonic peeling was performed at an ultrasonic power of 400 W for 3 h to obtain a sericite dispersion, the sericite dispersion was centrifuged once, the speed of the first centrifugation was 2000 r / min, the time of the first centrifugation was 20 min, the supernatant after the first centrifugation was centrifuged twice, the speed of the second centrifugation was 2000 r / min, the time of the second centrifugation was 20 min, the precipitate after the second centrifugation was washed and dried to obtain mica nanosheets;

[0151] (2) Deionized water, dichloromethane and ethanol were mixed in a volume ratio of 1:1.3:0.5 to obtain a composite solvent, acetic acid solution was added dropwise to the composite solvent to adjust its pH value to 4.5, silane coupling agent KH550 was added dropwise to the composite solvent, the volume ratio of silane coupling agent KH550 to the composite solvent was 1:15, and the mixture was stirred for 0.5 h to cause hydrolysis, thereby obtaining a silane coupling agent KH550 solution;

[0152] Dispersing the mica nanosheets obtained in step (1) in a silane coupling agent KH550 solution, wherein the ratio of the mica nanosheets to the silane coupling agent KH550 in the silane coupling agent KH550 solution is 1 g:0.05 mL, mixing and stirring for 60 minutes under a 70° C. water bath heating condition to react, and filtering, washing and drying after the reaction to obtain modified mica nanosheets;

[0153] (3) dispersing the modified mica nanosheets obtained in step (2) in deionized water to obtain a mica flake dispersion with a mass fraction of 8 wt%, and adding a manganese source solution to the mica flake dispersion under stirring, wherein the manganese source solution consists of potassium permanganate, manganese sulfate and deionized water, wherein the concentration of potassium permanganate is 7 g / mL, the mass ratio of potassium permanganate to manganese sulfate is 6:1, and the mass ratio of the modified mica nanosheets to potassium permanganate is 1:0.1; after all the manganese source solution is added dropwise, the mixture is mixed evenly, and then transferred to a hydrothermal reactor, and a hydrothermal reaction is performed at 130° C. for 5 h to obtain an intermediate reaction solution;

[0154] Subsequently, a hydrochloric acid solution with a concentration of 5 mol / L is added dropwise to the intermediate reaction solution to adjust its pH value to 5, and a tetrabutyl titanate solution is added dropwise to the intermediate reaction solution under stirring, wherein the tetrabutyl titanate solution consists of tetrabutyl titanate, ethanol and deionized water, wherein the volume ratio of tetrabutyl titanate, ethanol and deionized water is 10:80:40, and the mass ratio of the modified mica nanosheets to tetrabutyl titanate is 1:0.5. After all the tetrabutyl titanate solution is added dropwise, the mixture is mixed evenly, and then transferred to a hydrothermal reactor, and a secondary hydrothermal reaction is carried out at 150° C. for 6 hours, and then filtered, washed and dried to obtain the loaded modified mica nanosheets;

[0155] (4) steam-exploding the cellulose raw material to obtain raw fiber, wherein the steam pressure of the steam explosion is 1 MPa, the steam temperature is 180° C., and the processing time of the steam explosion is 10 min;

[0156] The raw material fiber, diammonium hydrogen phosphate, urea and deionized water are mixed to obtain a suspension, wherein the mass fraction of the raw material fiber in the suspension is 5wt%, the concentration of diammonium hydrogen phosphate is 0.2kg / L, and the concentration of urea is 0.4kg / L; the suspension is crushed at 60°C for 3h to obtain a mixed material; the mixed material is fed into a screw extruder, extruded and dehydrated at a speed of 10rpm to obtain a wet material with a moisture content of 60wt%;

[0157] The wet material is sequentially subjected to heating drying and high-temperature curing to obtain phosphorylated cellulose, wherein the heating drying temperature is 80° C., the heating drying time is 50 minutes, the high-temperature curing temperature is 150° C., and the high-temperature curing time is 30 minutes;

[0158] The phosphorylated cellulose is mixed with deionized water to obtain a cellulose mixed solution, wherein the mass fraction of the phosphorylated cellulose in the cellulose mixed solution is 0.5wt%, and the cellulose mixed solution is subjected to mechanical grinding and high-pressure homogenization in sequence, wherein the mechanical grinding is carried out in a colloid mill, the rotation speed of the colloid mill is 2500r / min, the mechanical grinding time is 3h, the high-pressure homogenization pressure is 70MPa, and the high-pressure homogenization time is 90min, and phosphorylated nanocellulose is obtained after high-pressure homogenization;

[0159] (5) the loaded modified mica nanosheets obtained in step (3), the phosphorylated nanocellulose obtained in step (4), the ethoxylated fatty acid ester and deionized water are uniformly mixed to obtain a composite suspension, wherein the mass fraction of the phosphorylated nanocellulose in the composite suspension is 1 wt %, the mass ratio of the phosphorylated nanocellulose to the loaded modified mica nanosheets is 1:3, and the mass fraction of the ethoxylated fatty acid ester is 0.5 wt %;

[0160] The composite suspension is ultrasonically dispersed for 3 hours at an ultrasonic power of 400 W to obtain a composite dispersion, and the composite dispersion is sent to a spray drying tower for spray drying. The inlet air temperature of the spray drying tower is 150°C, the outlet air temperature is 90°C, and the feeding speed is 50 mL / h. After spray drying, the nanocellulose-based reinforced modified material is obtained.

[0161] Figure 2 , Figure 3 and Figure 4 The scanning electron microscope images of the sericite used in this embodiment, the activated sericite prepared in this embodiment and the acidified sericite are shown in FIG. Figure 2 , the activated sericite obtained after high temperature activation treatment (such as Figure 3 The surface of the quartz crystal (as shown in Figure 2) has a rough structure, but the crystal structure is not completely destroyed and the lamellae morphology remains intact. Figure 3 , the acidified sericite (such as Figure 4 The lamella structure of the sericite mica is complete, the surface roughness structure has increased, wrinkles and cracks appear on the surface, and the surface area of ​​the sericite mica lamellae is increased, which is beneficial to the adsorption of lithium ions and cation exchange during the lithiation process.

[0162] Figure 5 The infrared spectra of sericite and mica nanosheets prepared in this example are shown in the figure. It can be seen from the figure that 3622cm -1 and 3448cm -1 The stretching vibration peaks of free water between sericite layers and free -OH on the surface are 1028 cm -1 The peak corresponding to the stretching vibration of Si-O-Si skeleton of sericite is 400~800cm -1The corresponding Al-O and Si-O bending vibration peaks are found in the infrared spectra of sericite and mica nanosheets, indicating that both contain sericite. The difference is that in the infrared spectra of mica nanosheets, 2918cm -1 and 2851cm -1 The corresponding positions are the antisymmetric -CH 3 and -CH 2 - stretching vibration peak, 1487cm -1 The peak at 1640 cm corresponds to the bending vibration peak of CN in the molecular chain of hexadecyltrimethylammonium bromide. -1 The corresponding CC absorption vibration peak indicates that the hexadecyl trimethyl ammonium bromide molecular chain has entered the sericite mica layer. In addition, in the infrared spectrum curve of the mica nanosheet modified by organic intercalation, 3622cm -1 The peak intensity at 3448cm -1 The peak intensity at 1028cm is enhanced, which is because the mica nanosheets modified by organic intercalation change from hydrophilic to hydrophobic, and the free water between the layers decreases. -1 The peak intensity at 4° is weakened because the molecular chain of hexadecyltrimethylammonium bromide enters the interlayers of sericite and destroys the skeleton structure to a certain extent.

[0163] Figure 6 and Figure 7 The AFM images of the bleached hardwood pulp used in this example and the raw material fiber prepared in this example are respectively: Figure 8 This is a transmission electron microscopy image of the phosphorylated nanocellulose prepared in this example. Figure 6 and Figure 7 By comparison, it can be seen that the size of the raw fiber obtained after steam explosion of bleached hardwood pulp becomes smaller, hemicellulose is partially dissolved, degraded and removed, cellulose is exposed, and a large number of spherical particles appear. These are lignin particles produced by the depolymerization of lignin in bleached hardwood pulp through the cleavage of aromatic ethers. Figure 7 and Figure 8 By comparison, it can be seen that nano-scale nanocellulose is obtained after mechanical grinding and high-pressure homogenization, with a diameter of about 15~20nm and a length of about 200~300nm.

[0164] Example 2

[0165] This embodiment provides a method for preparing an anti-aging nanocellulose-based enhanced modified material, such as Figure 1 As shown, the preparation method specifically comprises the following steps:

[0166] (1) calcining sericite at high temperature, wherein the heating temperature of the high temperature calcination is 780°C and the holding time is 1.8 hours, and activated sericite is obtained after calcination; the activated sericite is dispersed in a nitric acid solution with a concentration of 9 mol / L, and the ratio of the activated sericite to the nitric acid solution is 2.5 g:100 mL, and the mixture is mixed and stirred at 82°C for 4.8 hours, and then filtered, washed and dried to obtain acidified sericite; the acidified sericite and lithium nitrate are mixed uniformly at a mass ratio of 1:8.5 to obtain a mixed powder, and the mixed powder is fed into a muffle furnace, and calcined at 320°C for 5.8 hours to obtain a calcined powder, and the calcined powder is filtered, washed and dried to obtain lithiated sericite;

[0167] Dispersing lithiated sericite in deionized water, the mixing ratio of lithiated sericite to deionized water is 1 g:100 mL, and mixing evenly to obtain a sericite solution, adding hexadecyltrimethylammonium bromide to the sericite solution, the mass ratio of lithiated sericite to hexadecyltrimethylammonium bromide in the sericite solution is 1:2.8, mixing and stirring at 72° C. for 2.8 h, and then filtering, washing and drying to obtain intercalated sericite;

[0168] The intercalated sericite was dispersed in ethanol, the mass ratio of the intercalated sericite to ethanol was 1:4.2, ultrasonic stripping was performed at an ultrasonic power of 420 W for 2.8 h to obtain a sericite dispersion, the sericite dispersion was centrifuged once, the speed of the first centrifugation was 2200 r / min, the time of the first centrifugation was 18 min, the supernatant after the first centrifugation was centrifuged twice, the speed of the second centrifugation was 2200 r / min, the time of the second centrifugation was 18 min, the precipitate after the second centrifugation was washed and dried to obtain mica nanosheets;

[0169] (2) Deionized water, dichloromethane and ethanol were mixed in a volume ratio of 1:1.35:0.55 to obtain a composite solvent, acetic acid solution was added dropwise to the composite solvent to adjust its pH value to 4.8, silane coupling agent KH550 was added dropwise to the composite solvent, the volume ratio of silane coupling agent KH550 to the composite solvent was 1:16, and the mixture was stirred for 0.8 h to cause hydrolysis to obtain a silane coupling agent KH550 solution;

[0170] Dispersing the mica nanosheets obtained in step (1) in a silane coupling agent KH550 solution, wherein the ratio of the mica nanosheets to the silane coupling agent KH550 in the silane coupling agent KH550 solution is 1 g:0.052 mL, mixing and stirring for 50 minutes under a 72° C. water bath heating condition to react, and filtering, washing and drying after the reaction to obtain modified mica nanosheets;

[0171] (3) dispersing the modified mica nanosheets obtained in step (2) in deionized water to obtain a mica flake dispersion with a mass fraction of 8.5wt%, and adding a manganese source solution to the mica flake dispersion under stirring, wherein the manganese source solution consists of potassium permanganate, manganese sulfate and deionized water, wherein the concentration of potassium permanganate is 7.2g / mL, the mass ratio of potassium permanganate to manganese sulfate is 6.5:1, and the mass ratio of the modified mica nanosheets to potassium permanganate is 1:0.12; after all the manganese source solution is added dropwise, the mixture is mixed evenly, and then transferred to a hydrothermal reactor, and a hydrothermal reaction is carried out at 135°C for 4.8h to obtain an intermediate reaction solution;

[0172] Subsequently, a hydrochloric acid solution with a concentration of 6 mol / L was added dropwise to the intermediate reaction solution to adjust its pH value to 4.5, and a tetrabutyl titanate solution was added dropwise to the intermediate reaction solution under stirring, wherein the tetrabutyl titanate solution consisted of tetrabutyl titanate, ethanol and deionized water, wherein the volume ratio of tetrabutyl titanate, ethanol and deionized water was 12:85:42, and the mass ratio of the modified mica nanosheets to tetrabutyl titanate was 1:0.52. After all the tetrabutyl titanate solution was added dropwise, the mixture was mixed evenly, and then transferred to a hydrothermal reactor, and a secondary hydrothermal reaction was carried out at 152° C. for 5.8 hours, and then filtered, washed and dried to obtain the loaded modified mica nanosheets;

[0173] (4) steam explosion of the cellulose raw material to obtain raw fiber, wherein the steam pressure of the steam explosion is 1.2 MPa, the steam temperature is 185° C., and the processing time of the steam explosion is 8 min;

[0174] The raw material fiber, diammonium hydrogen phosphate, urea and deionized water are mixed to obtain a suspension, wherein the mass fraction of the raw material fiber in the suspension is 6wt%, the concentration of diammonium hydrogen phosphate is 0.22kg / L, and the concentration of urea is 0.42kg / L; the suspension is crushed at 65°C for 2.8h to obtain a mixed material; the mixed material is fed into a screw extruder, extruded and dehydrated at a speed of 12rpm to obtain a wet material with a moisture content of 62wt%;

[0175] The wet material is sequentially subjected to heating drying and high-temperature curing to obtain phosphorylated cellulose, wherein the heating drying temperature is 82° C., the heating drying time is 48 minutes, the high-temperature curing temperature is 152° C., and the high-temperature curing time is 28 minutes;

[0176] The phosphorylated cellulose is mixed with deionized water to obtain a cellulose mixed solution, wherein the mass fraction of the phosphorylated cellulose in the cellulose mixed solution is 0.8wt%, and the cellulose mixed solution is subjected to mechanical grinding and high-pressure homogenization in sequence, wherein the mechanical grinding is carried out in a colloid mill, the rotation speed of the colloid mill is 2600r / min, the mechanical grinding time is 2.8h, the pressure of the high-pressure homogenization is 80MPa, and the high-pressure homogenization time is 80min, and phosphorylated nanocellulose is obtained after high-pressure homogenization;

[0177] (5) the loaded modified mica nanosheets obtained in step (3), the phosphorylated nanocellulose obtained in step (4), the ethoxylated fatty acid ester and deionized water are uniformly mixed to obtain a composite suspension, wherein the mass fraction of the phosphorylated nanocellulose in the composite suspension is 1.2 wt %, the mass ratio of the phosphorylated nanocellulose to the loaded modified mica nanosheets is 1:3.5, and the mass fraction of the ethoxylated fatty acid ester is 0.8 wt %;

[0178] The composite suspension is ultrasonically dispersed for 2.8 hours at an ultrasonic power of 420 W to obtain a composite dispersion, and the composite dispersion is sent to a spray drying tower for spray drying. The inlet air temperature of the spray drying tower is 180° C., the outlet air temperature is 92° C., and the feeding speed is 60 mL / h. After spray drying, the nanocellulose-based reinforced modified material is obtained.

[0179] Example 3

[0180] This embodiment provides a method for preparing an anti-aging nanocellulose-based enhanced modified material, such as Figure 1 As shown, the preparation method specifically comprises the following steps:

[0181] (1) calcining sericite at high temperature, wherein the heating temperature of the high temperature calcination is 800°C and the holding time is 1.5 hours, and activated sericite is obtained after calcination; the activated sericite is dispersed in a nitric acid solution with a concentration of 10 mol / L, and the ratio of the activated sericite to the nitric acid solution is 3 g:100 mL, and the mixture is mixed and stirred at 85°C for 4.5 hours, and then filtered, washed and dried to obtain acidified sericite; the acidified sericite and lithium nitrate are mixed uniformly in a mass ratio of 1:9 to obtain a mixed powder, and the mixed powder is fed into a muffle furnace, and calcined at 350°C for 5.5 hours to obtain a calcined powder, and the calcined powder is filtered, washed and dried to obtain lithiated sericite;

[0182] Dispersing lithiated sericite in deionized water, the mixing ratio of lithiated sericite to deionized water is 1.1 g:100 mL, and mixing evenly to obtain a sericite solution, adding hexadecyltrimethylammonium bromide to the sericite solution, the mass ratio of lithiated sericite to hexadecyltrimethylammonium bromide in the sericite solution is 1:3, mixing and stirring at 75°C for 2.5 hours, and then filtering, washing and drying to obtain intercalated sericite;

[0183] The intercalated sericite was dispersed in ethanol, the mass ratio of the intercalated sericite to ethanol was 1:4.5, ultrasonic stripping was performed at an ultrasonic power of 450 W for 2.5 h to obtain a sericite dispersion, the sericite dispersion was centrifuged once, the speed of the first centrifugation was 2500 r / min, the time of the first centrifugation was 15 min, the supernatant after the first centrifugation was centrifuged twice, the speed of the second centrifugation was 2500 r / min, the time of the second centrifugation was 15 min, the precipitate after the second centrifugation was washed and dried to obtain mica nanosheets;

[0184] (2) Deionized water, dichloromethane and ethanol were mixed in a volume ratio of 1:1.4:0.6 to obtain a composite solvent, acetic acid solution was added dropwise to the composite solvent to adjust its pH value to 5, silane coupling agent KH550 was added dropwise to the composite solvent, the volume ratio of silane coupling agent KH550 to the composite solvent was 1:17, and the mixture was stirred for 1 hour to cause hydrolysis to obtain a silane coupling agent KH550 solution;

[0185] Dispersing the mica nanosheets obtained in step (1) in a silane coupling agent KH550 solution, wherein the ratio of the mica nanosheets to the silane coupling agent KH550 in the silane coupling agent KH550 solution is 1 g:0.055 mL, mixing and stirring for 40 minutes under a 75° C. water bath heating condition to react, and filtering, washing and drying after the reaction to obtain modified mica nanosheets;

[0186] (3) dispersing the modified mica nanosheets obtained in step (2) in deionized water to obtain a mica flake dispersion with a mass fraction of 9 wt%, and adding a manganese source solution to the mica flake dispersion under stirring, wherein the manganese source solution consists of potassium permanganate, manganese sulfate and deionized water, wherein the concentration of potassium permanganate is 7.5 g / mL, the mass ratio of potassium permanganate to manganese sulfate is 7:1, and the mass ratio of the modified mica nanosheets to potassium permanganate is 1:0.15; after all the manganese source solution is added dropwise, the mixture is mixed evenly, and then transferred to a hydrothermal reactor, and a hydrothermal reaction is performed at 140° C. for 4.5 hours to obtain an intermediate reaction solution;

[0187] Subsequently, a hydrochloric acid solution with a concentration of 7 mol / L was added dropwise to the intermediate reaction solution to adjust its pH value to 4, and a tetrabutyl titanate solution was added dropwise to the intermediate reaction solution under stirring, wherein the tetrabutyl titanate solution consisted of tetrabutyl titanate, ethanol and deionized water, wherein the volume ratio of tetrabutyl titanate, ethanol and deionized water was 15:90:45, and the mass ratio of the modified mica nanosheets to tetrabutyl titanate was 1:0.55. After all the tetrabutyl titanate solution was added dropwise, the mixture was mixed evenly, and then transferred to a hydrothermal reactor, and a secondary hydrothermal reaction was carried out at 155° C. for 5.5 hours, and then filtered, washed and dried to obtain the loaded modified mica nanosheets;

[0188] (4) steam-exploding the cellulose raw material to obtain raw fiber, wherein the steam pressure of the steam explosion is 1.5 MPa, the steam temperature is 190° C., and the processing time of the steam explosion is 7 min;

[0189] The raw material fiber, diammonium phosphate, urea and deionized water are mixed to obtain a suspension, wherein the mass fraction of the raw material fiber in the suspension is 7wt%, the concentration of diammonium phosphate is 0.25kg / L, and the concentration of urea is 0.45kg / L; the suspension is crushed at 70°C for 2.5h to obtain a mixed material; the mixed material is fed into a screw extruder, extruded and dehydrated at a speed of 15rpm to obtain a wet material with a moisture content of 65wt%;

[0190] The wet material is sequentially subjected to heating drying and high-temperature curing to obtain phosphorylated cellulose, wherein the heating drying temperature is 85° C., the heating drying time is 45 minutes, the high-temperature curing temperature is 155° C., and the high-temperature curing time is 25 minutes;

[0191] The phosphorylated cellulose is mixed with deionized water to obtain a cellulose mixed solution, wherein the mass fraction of the phosphorylated cellulose in the cellulose mixed solution is 1wt%, and the cellulose mixed solution is subjected to mechanical grinding and high-pressure homogenization in sequence, wherein the mechanical grinding is carried out in a colloid mill, the rotation speed of the colloid mill is 2700r / min, the mechanical grinding time is 2.5h, the pressure of the high-pressure homogenization is 90MPa, and the high-pressure homogenization time is 80min, and phosphorylated nanocellulose is obtained after high-pressure homogenization;

[0192] (5) the loaded modified mica nanosheets obtained in step (3), the phosphorylated nanocellulose obtained in step (4), alkanolamide and deionized water are uniformly mixed to obtain a composite suspension, wherein the mass fraction of the phosphorylated nanocellulose in the composite suspension is 1.5 wt %, the mass ratio of the phosphorylated nanocellulose to the loaded modified mica nanosheets is 1:4, and the mass fraction of the alkanolamide is 1 wt %;

[0193] The composite suspension is ultrasonically dispersed for 2.5 hours at an ultrasonic power of 450 W to obtain a composite dispersion, and the composite dispersion is sent to a spray drying tower for spray drying. The inlet air temperature of the spray drying tower is 200° C., the outlet air temperature is 95° C., and the feeding speed is 70 mL / h. After spray drying, the nanocellulose-based reinforced modified material is obtained.

[0194] Example 4

[0195] This embodiment provides a method for preparing an anti-aging nanocellulose-based enhanced modified material, such as Figure 1 As shown, the preparation method specifically comprises the following steps:

[0196] (1) calcining sericite at high temperature, wherein the heating temperature of the high temperature calcination is 820°C and the holding time is 1.2 hours, and activated sericite is obtained after calcination; the activated sericite is dispersed in a nitric acid solution with a concentration of 11 mol / L, and the ratio of the activated sericite to the nitric acid solution is 3.5 g:100 mL, and the mixture is mixed and stirred at 88°C for 4.2 hours, and then filtered, washed and dried to obtain acidified sericite; the acidified sericite and lithium nitrate are mixed uniformly at a mass ratio of 1:9.5 to obtain a mixed powder, and the mixed powder is fed into a muffle furnace, and calcined at 380°C for 5.2 hours to obtain a calcined powder, and the calcined powder is filtered, washed and dried to obtain lithiated sericite;

[0197] Dispersing lithiated sericite in deionized water, the mixing ratio of lithiated sericite to deionized water is 1.2 g:100 mL, and mixing evenly to obtain a sericite solution, adding hexadecyltrimethylammonium bromide to the sericite solution, the mass ratio of lithiated sericite to hexadecyltrimethylammonium bromide in the sericite solution is 1:3.2, mixing and stirring at 78° C. for 2.2 h, and then filtering, washing and drying to obtain intercalated sericite;

[0198] The intercalated sericite was dispersed in ethanol, the mass ratio of the intercalated sericite to ethanol was 1:4.8, ultrasonic stripping was performed at an ultrasonic power of 480 W for 2.2 h to obtain a sericite dispersion, the sericite dispersion was centrifuged once, the speed of the first centrifugation was 2800 r / min, the time of the first centrifugation was 12 min, the supernatant after the first centrifugation was centrifuged twice, the speed of the second centrifugation was 2800 r / min, the time of the second centrifugation was 12 min, the precipitate after the second centrifugation was washed and dried to obtain mica nanosheets;

[0199] (2) Deionized water, dichloromethane and ethanol were mixed in a volume ratio of 1:1.45:0.65 to obtain a composite solvent, acetic acid solution was added dropwise to the composite solvent to adjust its pH value to 5.2, silane coupling agent KH560 was added dropwise to the composite solvent, the volume ratio of silane coupling agent KH560 to the composite solvent was 1:18, and the mixture was stirred for 1.2 hours to cause hydrolysis, thereby obtaining a silane coupling agent KH560 solution;

[0200] Dispersing the mica nanosheets obtained in step (1) in a silane coupling agent KH560 solution, wherein the ratio of the mica nanosheets to the silane coupling agent KH560 in the silane coupling agent KH560 solution is 1 g:0.058 mL, mixing and stirring for 40 minutes under a 78° C. water bath heating condition to react, and filtering, washing and drying after the reaction to obtain modified mica nanosheets;

[0201] (3) dispersing the modified mica nanosheets obtained in step (2) in deionized water to obtain a mica flake dispersion with a mass fraction of 9.5wt%, and adding a manganese source solution to the mica flake dispersion under stirring, wherein the manganese source solution consists of potassium permanganate, manganese sulfate and deionized water, wherein the concentration of potassium permanganate is 7.8g / mL, the mass ratio of potassium permanganate to manganese sulfate is 7.5:1, and the mass ratio of the modified mica nanosheets to potassium permanganate is 1:0.18; after all the manganese source solution is added, the mixture is mixed evenly, and then transferred to a hydrothermal reactor, and a hydrothermal reaction is carried out at 145°C for 4.2h to obtain an intermediate reaction solution;

[0202] Subsequently, a hydrochloric acid solution with a concentration of 8 mol / L was added dropwise to the intermediate reaction solution to adjust its pH value to 3.5, and a tetrabutyl titanate solution was added dropwise to the intermediate reaction solution under stirring, wherein the tetrabutyl titanate solution consisted of tetrabutyl titanate, ethanol and deionized water, wherein the volume ratio of tetrabutyl titanate, ethanol and deionized water was 18:95:48, and the mass ratio of the modified mica nanosheets to tetrabutyl titanate was 1:0.58. After all the tetrabutyl titanate solution was added dropwise, the mixture was mixed evenly, and then transferred to a hydrothermal reactor, and a secondary hydrothermal reaction was carried out at 158° C. for 5.2 h, and then filtered, washed and dried to obtain the loaded modified mica nanosheets;

[0203] (4) steam explosion of the cellulose raw material to obtain raw fiber, wherein the steam pressure of the steam explosion is 1.8 MPa, the steam temperature is 195° C., and the processing time of the steam explosion is 6 min;

[0204] The raw material fiber, disodium hydrogen phosphate, urea and deionized water are mixed to obtain a suspension, wherein the mass fraction of the raw material fiber in the suspension is 8wt%, the concentration of disodium hydrogen phosphate is 0.28kg / L, and the concentration of urea is 0.48kg / L; the suspension is crushed at 75°C for 2.2h to obtain a mixed material; the mixed material is fed into a screw extruder, extruded and dehydrated at a speed of 18rpm to obtain a wet material with a moisture content of 68wt%;

[0205] The wet material is sequentially subjected to heating drying and high-temperature curing to obtain phosphorylated cellulose, wherein the heating drying temperature is 88° C., the heating drying time is 42 minutes, the high-temperature curing temperature is 158° C., and the high-temperature curing time is 22 minutes;

[0206] The phosphorylated cellulose is mixed with deionized water to obtain a cellulose mixed solution, wherein the mass fraction of the phosphorylated cellulose in the cellulose mixed solution is 1.2wt%, and the cellulose mixed solution is subjected to mechanical grinding and high-pressure homogenization in sequence, wherein the mechanical grinding is carried out in a colloid mill, the rotation speed of the colloid mill is 2800r / min, the mechanical grinding time is 2.2h, the pressure of the high-pressure homogenization is 90MPa, and the high-pressure homogenization time is 70min, and phosphorylated nanocellulose is obtained after high-pressure homogenization;

[0207] (5) The loaded modified mica nanosheets obtained in step (3), the phosphorylated nanocellulose obtained in step (4), the fatty alcohol polyoxyethylene ether and deionized water are uniformly mixed to obtain a composite suspension, wherein the mass fraction of the phosphorylated nanocellulose in the composite suspension is 1.8wt%, the mass ratio of the phosphorylated nanocellulose to the loaded modified mica nanosheets is 1:4.5, and the mass fraction of the fatty alcohol polyoxyethylene ether is 1.2wt%;

[0208] The composite suspension was ultrasonically dispersed for 2.2 hours at an ultrasonic power of 480 W to obtain a composite dispersion, and the composite dispersion was sent to a spray drying tower for spray drying. The inlet air temperature of the spray drying tower was 220° C., the outlet air temperature was 98° C., and the feeding speed was 80 mL / h. After spray drying, the nanocellulose-based reinforced modified material was obtained.

[0209] Example 5

[0210] This embodiment provides a method for preparing an anti-aging nanocellulose-based enhanced modified material, such as Figure 1 As shown, the preparation method specifically comprises the following steps:

[0211] (1) calcining sericite at high temperature, wherein the heating temperature of the high temperature calcination is 850°C and the holding time is 1 hour, and activated sericite is obtained after calcination; the activated sericite is dispersed in a nitric acid solution with a concentration of 12 mol / L, and the ratio of the activated sericite to the nitric acid solution is 4 g:100 mL, and the mixture is mixed and stirred at 90°C for 4 hours, and then filtered, washed and dried to obtain acidified sericite; the acidified sericite and lithium nitrate are mixed uniformly at a mass ratio of 1:10 to obtain a mixed powder, and the mixed powder is fed into a muffle furnace, and calcined at 400°C for 5 hours to obtain a calcined powder, and the calcined powder is filtered, washed and dried to obtain lithiated sericite;

[0212] Dispersing lithiated sericite in deionized water, the mixing ratio of lithiated sericite to deionized water is 1.3 g:100 mL, and mixing evenly to obtain a sericite solution, adding hexadecyltrimethylammonium bromide to the sericite solution, the mass ratio of lithiated sericite to hexadecyltrimethylammonium bromide in the sericite solution is 1:3.5, mixing and stirring at 80° C. for 2 h, and then filtering, washing and drying to obtain intercalated sericite;

[0213] The intercalated sericite was dispersed in ethanol, the mass ratio of the intercalated sericite to ethanol was 1:5, ultrasonic peeling was performed at an ultrasonic power of 500 W for 2 h to obtain a sericite dispersion, the sericite dispersion was centrifuged once, the speed of the first centrifugation was 3000 r / min, the time of the first centrifugation was 10 min, the supernatant after the first centrifugation was centrifuged twice, the speed of the second centrifugation was 3000 r / min, the time of the second centrifugation was 10 min, the precipitate after the second centrifugation was washed and dried to obtain mica nanosheets;

[0214] (2) Deionized water, dichloromethane and ethanol were mixed in a volume ratio of 1:1.5:0.7 to obtain a composite solvent, acetic acid solution was added dropwise to the composite solvent to adjust its pH value to 5.5, silane coupling agent KH560 was added dropwise to the composite solvent, the volume ratio of silane coupling agent KH560 to the composite solvent was 1:20, and the mixture was stirred for 1.5 hours to cause hydrolysis, thereby obtaining a silane coupling agent KH560 solution;

[0215] Dispersing the mica nanosheets obtained in step (1) in a silane coupling agent KH560 solution, wherein the ratio of the mica nanosheets to the silane coupling agent KH560 in the silane coupling agent KH560 solution is 1 g:0.06 mL, mixing and stirring for 30 minutes under a water bath heating condition of 80° C. to react, and filtering, washing and drying after the reaction to obtain modified mica nanosheets;

[0216] (3) dispersing the modified mica nanosheets obtained in step (2) in deionized water to obtain a mica flake dispersion with a mass fraction of 10 wt%, and adding a manganese source solution to the mica flake dispersion under stirring, wherein the manganese source solution consists of potassium permanganate, manganese sulfate and deionized water, wherein the concentration of potassium permanganate is 8 g / mL, the mass ratio of potassium permanganate to manganese sulfate is 8:1, and the mass ratio of the modified mica nanosheets to potassium permanganate is 1:0.2; after all the manganese source solution is added dropwise, the mixture is mixed evenly, and then transferred to a hydrothermal reactor, and a hydrothermal reaction is performed at 150° C. for 4 hours to obtain an intermediate reaction solution;

[0217] Subsequently, a hydrochloric acid solution with a concentration of 10 mol / L is added dropwise to the intermediate reaction solution to adjust its pH value to 3, and a tetrabutyl titanate solution is added dropwise to the intermediate reaction solution under stirring, wherein the tetrabutyl titanate solution consists of tetrabutyl titanate, ethanol and deionized water, wherein the volume ratio of tetrabutyl titanate, ethanol and deionized water is 20:100:50, and the mass ratio of modified mica nanosheets to tetrabutyl titanate is 1:0.6. After all the tetrabutyl titanate solution is added dropwise, the mixture is mixed evenly, and then transferred to a hydrothermal reactor, and a secondary hydrothermal reaction is carried out at 160° C. for 5 hours, and then filtered, washed and dried to obtain loaded modified mica nanosheets;

[0218] (4) steam explosion of the cellulose raw material to obtain raw fiber, wherein the steam pressure of the steam explosion is 2 MPa, the steam temperature is 200° C., and the processing time of the steam explosion is 5 min;

[0219] The raw material fiber, sodium dihydrogen phosphate, urea and deionized water are mixed to obtain a suspension, wherein the mass fraction of the raw material fiber in the suspension is 10wt%, the concentration of sodium dihydrogen phosphate is 0.3kg / L, and the concentration of urea is 0.5kg / L; the suspension is crushed at 80°C for 2h to obtain a mixed material; the mixed material is fed into a screw extruder, extruded and dehydrated at a speed of 20rpm to obtain a wet material with a moisture content of 70wt%;

[0220] The wet material is sequentially subjected to heating and drying and high-temperature curing to obtain phosphorylated cellulose, wherein the heating and drying temperature is 90° C., the heating and drying time is 40 minutes, the high-temperature curing temperature is 160° C., and the high-temperature curing time is 20 minutes;

[0221] The phosphorylated cellulose is mixed with deionized water to obtain a cellulose mixed solution, wherein the mass fraction of the phosphorylated cellulose in the cellulose mixed solution is 1.5wt%, and the cellulose mixed solution is subjected to mechanical grinding and high-pressure homogenization in sequence, wherein the mechanical grinding is carried out in a colloid mill, the rotation speed of the colloid mill is 3000r / min, the mechanical grinding time is 2h, the pressure of the high-pressure homogenization is 100MPa, and the high-pressure homogenization time is 60min, and phosphorylated nanocellulose is obtained after high-pressure homogenization;

[0222] (5) the loaded modified mica nanosheets obtained in step (3), the phosphorylated nanocellulose obtained in step (4), the fatty alcohol polyoxyethylene ether and deionized water are uniformly mixed to obtain a composite suspension, wherein the mass fraction of the phosphorylated nanocellulose in the composite suspension is 2 wt %, the mass ratio of the phosphorylated nanocellulose to the loaded modified mica nanosheets is 1:5, and the mass fraction of the fatty alcohol polyoxyethylene ether is 1.5 wt %;

[0223] The composite suspension is ultrasonically dispersed for 2 hours at an ultrasonic power of 500 W to obtain a composite dispersion, and the composite dispersion is sent to a spray drying tower for spray drying. The inlet air temperature of the spray drying tower is 250° C., the outlet air temperature is 100° C., and the feeding speed is 100 mL / h. After spray drying, the nanocellulose-based reinforced modified material is obtained.

[0224] Example 6

[0225] This embodiment provides a method for preparing an anti-aging nanocellulose-based reinforced modified material. The difference from Example 1 is that in step (3), the mass ratio of the modified mica nanosheets to the potassium permanganate in the manganese source solution is adjusted to 1:0.05, and the other process parameters and operating steps are exactly the same as those in Example 1.

[0226] Example 7

[0227] This embodiment provides a method for preparing an anti-aging nanocellulose-based reinforced modified material. The difference from Example 1 is that in step (3), the mass ratio of the modified mica nanosheets to the potassium permanganate in the manganese source solution is adjusted to 1:0.3, and the other process parameters and operating steps are exactly the same as those in Example 1.

[0228] Example 8

[0229] This embodiment provides a method for preparing an anti-aging nanocellulose-based reinforced modified material. The difference from Example 1 is that in step (3), a hydrochloric acid solution with a concentration of 5 mol / L is added dropwise to the intermediate reaction solution to adjust its pH value to 2. The other process parameters and operating steps are exactly the same as those in Example 1.

[0230] Example 9

[0231] This embodiment provides a method for preparing an anti-aging nanocellulose-based reinforced modified material. The difference from Embodiment 1 is that in step (3), a 5 mol / L hydrochloric acid solution is added dropwise to the intermediate reaction solution to adjust its pH value to 6. The other process parameters and operation steps are exactly the same as those in Embodiment 1.

[0232] Example 10

[0233] This embodiment provides a method for preparing an anti-aging nanocellulose-based reinforced modified material. The difference from Example 1 is that in step (3), the mass ratio of modified mica nanosheets to tetrabutyl titanate in the tetrabutyl titanate solution is adjusted to 1:0.3, and the other process parameters and operating steps are exactly the same as those in Example 1.

[0234] Embodiment 11

[0235] This embodiment provides a method for preparing an anti-aging nanocellulose-based reinforced modified material. The difference from Example 1 is that in step (3), the mass ratio of modified mica nanosheets to tetrabutyl titanate in the tetrabutyl titanate solution is adjusted to 1:0.8, and the other process parameters and operating steps are exactly the same as those in Example 1.

[0236] Example 12

[0237] This embodiment provides a method for preparing an anti-aging nanocellulose-based reinforced modified material. The difference from Example 1 is that in step (4), the mass ratio of phosphorylated nanocellulose to loaded modified mica nanosheets is adjusted to 1:2, and the other process parameters and operating steps are exactly the same as those in Example 1.

[0238] Embodiment 13

[0239] This embodiment provides a method for preparing an anti-aging nanocellulose-based reinforced modified material. The difference from Example 1 is that in step (4), the mass ratio of phosphorylated nanocellulose to loaded modified mica nanosheets is adjusted to 1:6, and the other process parameters and operating steps are exactly the same as those in Example 1.

[0240] Application Examples

[0241] This application example provides a water-based coating, which includes the following components in parts by weight:

[0242] 80 parts of styrene acrylic emulsion;

[0243] 10 parts water;

[0244] 5 parts of ethylene glycol butyl ether;

[0245] 3 parts of nanocellulose-based reinforced modified material;

[0246] BYK-141 defoamer 1 part;

[0247] BYK-346 wetting agent 0.5 parts;

[0248] 0.5 parts of BYK-300 leveling agent.

[0249] Among them, the nanocellulose-based enhanced modified material is the nanocellulose-based enhanced modified material prepared in each embodiment of the present invention.

[0250] According to the formula of the water-based coating provided in this application example, water-based coatings were prepared using the nanocellulose-based reinforced modified materials provided in Examples 1-13, and were named water-based coating 1, water-based coating 2, water-based coating 3, water-based coating 4, water-based coating 5, water-based coating 6, water-based coating 7, water-based coating 8, water-based coating 9, water-based coating 10, water-based coating 11, water-based coating 12 and water-based coating 13 (hereinafter referred to as water-based coatings 1-13).

[0251] Comparative Example

[0252] This comparative example provides a water-based coating, which includes the following components in parts by weight:

[0253] 80 parts of styrene acrylic emulsion;

[0254] 10 parts of deionized water;

[0255] 5 parts of ethylene glycol butyl ether;

[0256] BYK-420 thickener 3 parts;

[0257] BYK-141 defoamer 1 part;

[0258] BYK-346 wetting agent 0.5 parts;

[0259] 0.5 parts of BYK-300 leveling agent.

[0260] The various properties of water-based coatings 1-13 and the water-based coatings provided in the comparative examples were tested. The specific test steps are as follows:

[0261] (1) Pencil hardness test

[0262] The wood was made into a 120×10×2 mm sample strip, and the water-based coatings 1-13 and the water-based coatings provided in the comparative example were evenly coated on the surface, and the sample strips were dried and cured for 7 days. The pencil hardness of the paint film on the surface of the sample strip was tested by the scratch hardness method in accordance with the national standard GB / T6739-2022 "Determination of paint film hardness by pencil method for paints and varnishes".

[0263] (2) Washing resistance test

[0264] The wood was made into a 120×10×2 mm sample strip, and the water-based coatings 1-13 and the water-based coatings provided in the comparative example were evenly coated on the surface, and the sample strips were dried and cured for 7 days. Subsequently, the washability of the paint film was tested in a constant temperature and humidity environment of 23±2°C and 50±5%. The specific steps are as follows:

[0265] Dip the paint film surface of the sample strip in a washing powder solution with a pH value of 9.5-11.0 and a mass fraction of 0.5wt%, fix the sample strip on the scrub resistance tester, scrub the paint film surface repeatedly until the paint film is damaged, and stop the test, and record the number of scrubbing times.

[0266] (3) Limiting oxygen index test

[0267] The wood was made into a 120×10×2mm sample strip, and the water-based coatings 1-13 and the water-based coatings provided in the comparative example were evenly coated on the surface, and the sample strips were dried and cured for 7 days. The sample strips were tested for oxygen index using a JF-3 oxygen index tester in accordance with the national standard GB / T2406.2-2009 "Determination of combustion behavior of plastics by oxygen index method Part 2: Room temperature test". The limiting oxygen index is the minimum oxygen volume fraction required for continuous combustion of polymer materials in a mixture of nitrogen and oxygen. The specific test steps are as follows:

[0268] Place the sample strip vertically in a mixed atmosphere of oxygen and nitrogen, ignite the sample strip, and adjust the introduction ratio of oxygen and nitrogen so that the sample strip can just burn stably for 3 minutes. Record the oxygen concentration in the mixed atmosphere at this time, which is the limiting oxygen index of the sample strip.

[0269] (4) Aging resistance test

[0270] The wood was made into a 120×10×2mm sample strip, and the water-based paint 1-13 and the water-based paint provided in the comparative example were evenly coated on the surface, and the sample strip was dried and cured for 7 days. Referring to the national standard GB / T 14522-2008 "Artificial weathering test method for plastics, coatings, and rubber materials for mechanical industrial products - fluorescent ultraviolet lamp", the UVA-340 fluorescent lamp was used to test the anti-ultraviolet light oxidation of the paint film formed by the water-based paint 1-13 and the water-based paint provided in the comparative example, and the "4h irradiation (0.89W·m -2 ·nm -1 ) and 20h condensation", the total test time is 72h. After the test, the color difference value ΔE of the paint film is tested and calculated using a colorimeter to evaluate its aging resistance.

[0271] The testing process of the color difference ΔE of the paint film is as follows:

[0272] Randomly select a point on the paint film and use a colorimeter to measure the data L of the point 1 、a 1 , b 1 , where L 1 Indicates the brightness of the point, a 1 Indicates the red-green color change of the point, b 1 Indicates the yellow-blue color change of the point. Then, another point is randomly selected on the paint film and the colorimeter is used to measure the data of the other point L 2 、a 2 , b 2 , where L 2 Indicates the brightness of the point, a 2 Indicates the red-green color change of the point, b 2 Indicates the yellow-blue color change at that point.

[0273] The color difference of the paint film is calculated according to the following formula:

[0274]

[0275] Where ΔL=L 1 -L 2 , Δa=a 1 -a 2 , Δb=b 1 -b 2 .

[0276] The surface morphology of the paint film before and after the aging test was observed, and the following results were obtained: Fig. 9 , Fig.10 , Fig.11 and Fig.12 The electron microscope image shown, Fig. 9 and Fig.10They are surface electron microscope images of the paint film formed by water-based paint 1 (i.e., the water-based paint prepared by the nanocellulose-based reinforced modified material prepared in Example 1 according to the formula provided in the application example) before and after the aging test, Fig.11 and Fig.12 Surface electron micrographs of the paint films formed by the water-based paints provided as comparative examples before and after the aging test.

[0277] Depend on Fig. 9 and Fig.11 It can be seen that before the aging test, the surfaces of the paint films formed by the water-based coating 1 and the comparative example are relatively smooth, without cracks or bubbles. Fig. 9 The electron microscope image shown in the figure also shows the obvious lamellar structure of the loaded modified mica nanosheets. After 27 days of UV accelerated aging test, the following Fig.10 and Fig.12 The electron microscope images shown in the figure show that compared with before the aging test, Fig.10 and Fig.12 The surface smoothness of the paint film is reduced, but Fig.12 The roughness of the paint film surface is more serious. In addition, Fig.12 The paint film surface shown has undergone a lot of oxidation degradation and severe cracking and peeling.

[0278] Other test results are shown in Table 1.

[0279] Table 1

[0280] Pencil hardness Washing times Limiting oxygen index% Appearance of the paint film after 27 days of aging test Color difference of paint film after 24h aging test 𝛥𝐸 Color difference of paint film after 72h aging test 𝛥𝐸 Example 1 5H 1100 times 29.7 The paint film surface is smooth, without cracks or bubbles 0.8 2.2 Example 2 5H 1100 times 30.3 The paint film surface is smooth, without cracks or bubbles. 0.7 2 Example 3 5H 1200 times 32.1 The paint film surface is smooth, without cracks or bubbles 0.5 1.9 Example 4 6H 1200 times 32.6 The paint film surface is smooth, without cracks or bubbles 0.2 1.6 Example 5 5H 1200 times 33.5 The paint film surface is smooth, without cracks or bubbles 0.4 1.8 Example 6 4H 900 times 28.6 The paint film surface is rough, has severe cracks, and has severe bubbles. 3.5 6.7 Example 7 3H 800 times 29.0 The paint film surface is rough, cracked, and bubbling 1.8 4.5 Example 8 4H 1000 times 28.9 The paint film surface is rough, cracked, and bubbling 2.7 6.2 Example 9 4H 1000 times 29.2 The paint film surface is rough, cracked, and bubbling 2.2 5.3 Example 10 4H 900 times 28.1 The paint film surface is rough, has severe cracks, and has severe bubbles. 3.6 7.4 Embodiment 11 3H 800 times 28.7 The paint film surface is rough, has severe cracks, and has severe bubbles. 2 4.9 Example 12 3H 900 times 26.5 The paint film surface is rough, has severe cracks, and has severe bubbles. 3.8 7.8 Embodiment 13 HB 700 times 25.8 The paint film surface is relatively smooth, with slight cracks and no bubbles 1.2 3.1 Comparative Example 2B 500 times 24.3 The paint film surface is rough, has severe cracks, and has severe bubbles. 4.3 8.6

[0281] It can be seen from the test data provided in Table 1 that the pencil hardness, washability, limiting oxygen index, appearance of the paint film after aging test and color difference of the paint films prepared in Examples 1-13 are better than those of the comparative example, which indicates that the nanocellulose-based reinforced modified material prepared in the present invention can significantly improve the mechanical properties, flame retardant properties and anti-aging properties of the paint film.

[0282] It can be seen from the test data of Example 1, Example 6 and Example 7 that the pencil hardness, number of wash resistance, appearance after aging test and color difference of the paint films prepared in Example 6 and Example 7 are inferior to those in Example 1. This is because the amount of potassium permanganate used in Example 6 is too low, and the manganese dioxide generated by the hydrothermal synthesis reaction is too little, resulting in the crystal form of the generated titanium dioxide being mainly anatase, which significantly affects the anti-aging performance of the paint film. In Example 7, the amount of potassium permanganate used is too high, resulting in excessive manganese dioxide generated by the hydrothermal synthesis reaction, and agglomeration occurs on the surface of the modified mica nanosheets, which not only affects the mechanical properties of the paint film, but also affects the anti-aging performance of the paint film.

[0283] It can be seen from the test data of Example 1, Example 8 and Example 9 that the appearance and color difference of the paint films prepared by Example 8 and Example 9 after aging test are inferior to those of Example 1. This is because the pH value of the intermediate reaction solution in Example 8 is too low, and the pH value of the intermediate reaction solution in Example 9 is too high. The pH value has a great influence on the morphology, structure and crystal form of titanium dioxide loaded on the surface of the modified mica nanosheets. Too high or too low pH values ​​are not conducive to the generation of titanium dioxide particles with higher ultraviolet absorption intensity, which ultimately leads to a decrease in the anti-aging performance of the paint film.

[0284] It can be seen from the test data of Example 1, Example 10 and Example 11 that the pencil hardness, number of wash resistance, appearance after aging test and color difference of the paint film prepared by Example 10 and Example 11 are inferior to those of Example 1. This is because the amount of tetrabutyl titanate in Example 10 is too low, and the titanium dioxide generated by the hydrothermal synthesis reaction is too little, and the ultraviolet absorption ability of titanium dioxide cannot be fully exerted, which significantly affects the anti-aging performance of the paint film; the amount of tetrabutyl titanate in Example 11 is too high, and the titanium dioxide generated by the hydrothermal synthesis reaction is too much, resulting in a messy, loose and uneven coating state on the surface of the loaded modified mica nanosheets, and the photoreaction active sites are reduced, which not only affects the mechanical properties of the paint film, but also affects the anti-aging performance of the paint film.

[0285] It can be seen from the test data of Example 1, Example 12 and Example 13 that the appearance and color difference of the paint film prepared by Example 12 after the aging test are inferior to those of Example 1. This is because the amount of the loaded modified mica nanosheets in Example 12 is too low, and the advantages of the loaded modified mica nanosheets in anti-aging cannot be fully utilized. The pencil hardness, washing resistance and limiting oxygen index of the paint film prepared by Example 13 are inferior to those of Example 1. This is because the amount of the loaded modified mica nanosheets in Example 13 is too high, and the amount of phosphorylated nanocellulose is relatively low, and the advantages of phosphorylated nanocellulose in mechanical reinforcement and flame retardancy cannot be fully utilized.

[0286] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing an anti-aging nanocellulose-based enhanced modified material, characterized in that: The preparation method comprises: (I) subjecting sericite to high temperature calcination to obtain activated sericite; subjecting the activated sericite to acidification with a nitric acid solution to obtain acidified sericite; subjecting the acidified sericite to lithiation with lithium nitrate to obtain lithiated sericite; subjecting the lithiated sericite to intercalation modification with hexadecyltrimethylammonium bromide to obtain intercalated sericite; subjecting the intercalated sericite to ultrasonic exfoliation to obtain mica nanosheets; (II) mixing deionized water, dichloromethane and ethanol to obtain a composite solvent, and dropping an acetic acid solution into the composite solvent to adjust the pH value thereof; dropping a silane coupling agent into the composite solvent, mixing and stirring to cause hydrolysis, and obtaining a silane coupling agent solution; dispersing the mica nanosheets obtained in step (I) in the silane coupling agent solution, mixing and stirring under a water bath heating condition to cause a reaction, and filtering, washing and drying after the reaction to obtain modified mica nanosheets; (III) dispersing the modified mica nanosheets obtained in step (II) in deionized water to obtain a mica dispersion, adding a manganese source solution to the mica dispersion under stirring conditions, mixing evenly, and then performing a hydrothermal reaction to obtain an intermediate reaction solution; adding a tetrabutyl titanate solution to the intermediate reaction solution under stirring conditions, mixing evenly, and then performing a secondary hydrothermal reaction, and then filtering, washing and drying to obtain loaded modified mica nanosheets; (IV) sequentially subjecting the cellulose raw material to phosphorylation and nano-processing to obtain phosphorylated nanocellulose; uniformly mixing the phosphorylated nanocellulose, the loaded modified mica nanosheets obtained in step (III), a nonionic surfactant and deionized water to obtain a composite suspension, ultrasonically dispersing the composite suspension to obtain a composite dispersion, and spray-drying the composite dispersion to obtain the nanocellulose-based enhanced modified material.

2. The preparation method according to claim 1, characterized in that: In step (I), the heating temperature of the high temperature calcination is 750-850°C; The holding time of the high temperature calcination is 1 to 2 hours; The acidification process comprises: dispersing the activated sericite in a nitric acid solution, mixing, stirring and heating, and then filtering, washing and drying to obtain the acidified sericite; The concentration of the nitric acid solution is 8-12 mol / L; The ratio of the activated sericite to the nitric acid solution is (2-4) g:100 mL; The time for mixing and stirring the activated sericite and the nitric acid solution is 4 to 5 hours; The temperature of mixing and stirring the activated sericite and the nitric acid solution is 80-90° C.; The lithiation process comprises: The acidified sericite and lithium nitrate are uniformly mixed to obtain a mixed powder; the mixed powder is sent into a muffle furnace for calcination to obtain a calcined powder, and the calcined powder is filtered, washed and dried to obtain the lithiated sericite; The mass ratio of the acidified sericite to the lithium nitrate is 1:(8-10); The calcination temperature of the mixed powder is 300-400°C; The calcination time of the mixed powder is 5 to 6 hours.

3. The preparation method according to claim 2, characterized in that: In step (I), the intercalation modification process includes: Dispersing the lithiated sericite in deionized water to obtain a sericite solution, adding hexadecyltrimethylammonium bromide to the sericite solution, mixing, stirring and heating, and then filtering, washing and drying to obtain the intercalated sericite; The mixing ratio of the lithiated sericite and deionized water is (0.8-1.3) g:100 mL; The mass ratio of the lithiated sericite to hexadecyltrimethylammonium bromide in the sericite solution is 1:(2.5-3.5); The mixing and stirring time of the sericite solution and hexadecyltrimethylammonium bromide is 2 to 3 hours; The temperature for mixing and stirring the sericite solution and cetyltrimethylammonium bromide is 70-80°C.

4. The preparation method according to claim 1, characterized in that: In step (I), the ultrasonic peeling process includes: The intercalated sericite is dispersed in ethanol, and ultrasonic stripping is performed to obtain a sericite dispersion liquid, the sericite dispersion liquid is centrifuged once, the supernatant after the first centrifugation is taken for a second centrifugation, and the precipitate after the second centrifugation is washed and dried to obtain the mica nanosheets; The mass ratio of the intercalated sericite to ethanol is 1:(4-5); The ultrasonic power of the ultrasonic peeling is 400-500W; The ultrasonic peeling time is 2 to 3 hours; The rotation speed of the primary centrifugation is 2000-3000 r / min; The time of one centrifugation is 10 to 20 minutes; The secondary centrifugation speed is 2000-3000 r / min; The secondary centrifugation time is 10 to 20 minutes.

5. The preparation method according to claim 1, characterized in that: In step (II), the volume ratio of deionized water, dichloromethane and ethanol in the composite solvent is 1:(1.3-1.5):(0.5-0.7); Adding acetic acid solution dropwise to the composite solvent to adjust the pH value thereof to 4.5-5.5; The volume ratio of the silane coupling agent to the composite solvent is 1:(15-20); The mixing time of the silane coupling agent and the composite solvent is 0.5 to 1.5 hours; The ratio of the mica nanosheets to the silane coupling agent in the silane coupling agent solution is 1 g: (0.05-0.06) mL; The mixing time of the mica nanosheets and the silane coupling agent solution is 30 to 60 minutes; The temperature for mixing and stirring the mica nanosheets and the silane coupling agent solution is 70-80°C.

6. The preparation method according to claim 1, characterized in that: In step (III), the mass fraction of the modified mica nanosheets in the mica flake dispersion is 8-10wt%; The manganese source solution consists of potassium permanganate, manganese sulfate and deionized water; The concentration of potassium permanganate in the manganese source solution is 7-8 g / mL; In the manganese source solution, the mass ratio of potassium permanganate to manganese sulfate is (6-8):1; The mass ratio of the modified mica nanosheets to the potassium permanganate in the manganese source solution is 1:(0.1-0.2); The reaction temperature of the primary hydrothermal reaction is 130-150°C; The reaction time of the primary hydrothermal reaction is 4 to 5 hours; Before adding the tetrabutyl titanate solution to the intermediate reaction solution, firstly adding a hydrochloric acid solution to the intermediate reaction solution to adjust the pH value thereof to 3-5; The concentration of the hydrochloric acid solution is 5-10 mol / L; The tetrabutyl titanate solution consists of tetrabutyl titanate, ethanol and deionized water; In the tetrabutyl titanate solution, the volume ratio of tetrabutyl titanate, ethanol and deionized water is (10-20):(80-100):(40-50); The mass ratio of the modified mica nanosheets to the tetrabutyl titanate in the tetrabutyl titanate solution is 1:(0.5-0.6); The reaction temperature of the secondary hydrothermal reaction is 150-160°C; The reaction time of the secondary hydrothermal reaction is 5 to 6 hours.

7. The preparation method according to claim 1, characterized in that: In step (IV), the phosphorylation treatment comprises: The cellulose raw material is subjected to steam explosion to obtain raw fiber, the raw fiber, phosphate, urea and deionized water are mixed to obtain a suspension, the suspension is heated and crushed at the same time to obtain a mixed material; the mixed material is sent to a screw extruder for extrusion dehydration to obtain a wet material; the wet material is sequentially heated and dried and high-temperature cured to obtain phosphorylated cellulose; The cellulose raw material includes bleached hardwood pulp or bleached softwood pulp; The steam pressure of the steam explosion is 1-2 MPa; The steam temperature of the steam explosion is 180-200°C; The processing time of the steam explosion is 5 to 10 minutes; The mass fraction of the raw material fiber in the suspension is 5-10wt%; The concentration of phosphate in the suspension is 0.2-0.3 kg / L; The phosphate includes any one of diammonium hydrogen phosphate, ammonium dihydrogen phosphate, disodium hydrogen phosphate, sodium dihydrogen phosphate, dilithium hydrogen phosphate or lithium dihydrogen phosphate, or a combination of at least two thereof; The concentration of urea in the suspension is 0.4-0.5 kg / L; The heating temperature of the suspension is 60-80°C; The heating time of the suspension is 2 to 3 hours; The screw speed of the screw extruder is 10-20 rpm; The moisture content of the wet material is 60-70wt%; The heating and drying temperature is 80-90°C; The heating and drying time is 40 to 50 minutes; The high temperature curing temperature is 150-160°C; The high temperature curing time is 20 to 30 minutes.

8. The preparation method according to claim 7, characterized in that: In step (IV), the nano-processing steps include: The phosphorylated cellulose is mixed with deionized water to obtain a cellulose mixed solution, and the cellulose mixed solution is subjected to mechanical grinding and high-pressure homogenization in sequence to obtain the phosphorylated nanocellulose; The mass fraction of the phosphorylated cellulose in the cellulose mixed solution is 0.5-1.5wt%; The mechanical grinding is carried out in a colloid mill; The rotation speed of the colloid mill is 2500-3000 r / min; The mechanical grinding time is 2 to 3 hours; The pressure of the high pressure homogenization is 70-100 MPa; The high pressure homogenization time is 60 to 90 minutes.

9. The preparation method according to claim 1, characterized in that: In step (IV), the mass fraction of the phosphorylated nanocellulose in the composite suspension is 1-2 wt %; The mass ratio of the phosphorylated nanocellulose to the loaded modified mica nanosheets is 1:(3-5); The mass fraction of the nonionic surfactant in the composite suspension is 0.5-1.5wt%; The nonionic surfactant includes any one or a combination of at least two of ethoxylated fatty acid esters, alkanolamides or fatty alcohol polyoxyethylene ethers; The ultrasonic power of the ultrasonic dispersion of the composite suspension is 400-500W; The ultrasonic dispersion time of the composite suspension is 2 to 3 hours; The spray drying process of the composite dispersion is carried out in a spray drying tower; The air inlet temperature of the spray drying tower is 150-250°C; The outlet air temperature of the spray drying tower is 90-100°C; The feeding speed of the spray drying tower is 50-100 mL / h.

10. An anti-aging nanocellulose-based reinforced modified material prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Cited By

  • Heat-shrinkage-resistant PE isolating membrane base membrane and preparation method thereof

    CN119823429A